Solid oxide battery having a porous layer and method for producing the same

By integrating porous layers and electrocatalytic infiltration at reduced temperatures, the performance and efficiency of solid oxide electrochemical cells are enhanced, addressing the challenges of ohmic loss and slow kinetics in conventional SOCs.

JP2025501615AInactive Publication Date: 2025-01-22MARYLAND COLLEGE PARK UNIV OF
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024538320
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-12-22
Publication Date
2025-01-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional solid oxide electrochemical cells (SOCs) face challenges in lowering operating temperatures due to increased ohmic loss and slow oxygen reduction reaction kinetics, which reduce performance and efficiency, particularly in ceria-based electrolytes under reducing conditions.

Method used

Incorporating porous layers on the oxygen side of a non-porous oxide layer, configured as electrodes, and performing electrocatalytic infiltration at temperatures below 1000°C to maintain high oxygen transport and electronic connectivity, while using a porous functional layer to limit electronic conductivity and enhance ion transfer.

Benefits of technology

This configuration achieves higher open circuit voltage and lower area specific resistance, improving SOC performance at lower temperatures, with enhanced efficiency and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501615000001_ABST
    Figure 2025501615000001_ABST
Patent Text Reader

Abstract

The solid oxide battery may include a non-porous oxide layer, one or more first porous layers, and one or more second porous layers. The non-porous oxide layer may conduct oxygen ions and may operate as a solid electrolyte. The first and second porous layers may be disposed on opposite sides of the non-porous oxide layer. The non-porous oxide layer may have a density greater than the respective densities of the first and second porous layers. In some embodiments, at least one of the one or more first porous layers may be infiltrated with one or more electrocatalyst oxides. Alternatively, in some embodiments, a porous functional layer may be disposed between the non-porous oxide layer and the one or more first porous layers. The porous functional layer may be effective in increasing the open circuit voltage of the solid oxide battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS-REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of U.S. Provisional Application No. 63 / 265,920, filed December 22, 2021, entitled "Scaffold-Permeated Cathode for Low-Temperature Solid Oxide Fuel Cells," and U.S. Provisional Application No. 63 / 265,921, filed December 22, 2021, entitled "Porous Ceria-Based Functional Layer for Solid Oxide Cells," each of which is incorporated herein in its entirety.

[0002] (Statement Regarding Federally Sponsored Research) This invention was made with U.S. Government support under DEFED0031662 awarded by the U.S. Department of Energy's Office of Fossil Energy, and DEAR0001345 awarded by the U.S. Department of Energy's Advanced Research Projects Office-Energy (DOE ARPA-E). The U.S. Government has certain rights in this invention.

[0003] FIELD OF THE DISCLOSURE This disclosure relates generally to solid oxide electrochemical cells, and more particularly to solid oxide electrochemical cells having a porous layer to enhance their low temperature performance. [Background technology]

[0004] Solid oxide electrochemical cells (SOCs) are at the forefront of clean energy research to mitigate the effects of climate change. SOCs can operate in a fuel cell mode (e.g., solid oxide fuel cells or SOFCs) to generate electricity from chemical fuels, or in an electrolysis mode (e.g., solid oxide electrolysis cells or SOECs) to use electricity to generate chemical fuels that can be stored for future use. In traditional SOCs, high temperatures (e.g., >800°C) are required to thermally activate the oxygen ion transport and electrode reaction processes. However, such high temperatures also result in degradation issues. Therefore, lowering the operating temperature of SOCs could help advance their adoption and commercialization. One of the challenges for lowering the operating temperature is that ohmic losses in the electrolyte increase with decreasing temperature, thereby decreasing SOC performance. In addition, the sluggish kinetics of the oxygen reduction reaction (ORR) at the cathode may limit performance at low temperatures (e.g., <650°C). Summary of the Invention [Problem to be solved by the invention]

[0005] Among conventional solid oxide electrolytes, doped ceria (e.g., Ce 1-x Gd x O 2-δ and Ce 1-x Sm x O 2-δ ) may be an attractive option for low temperature applications due to their higher oxygen ion conductivity. However, cerium can be converted to Ce under reducing conditions. 4+ / Ce 3+ Because they undergo redox couples, ceria-based electrolytes are mixed ionic and electronic conductors. This can lead to lower open circuit voltages (OCVs) for SOECs than theoretical values, reducing the efficiency of the device. In addition, for SOECs where electricity is converted to chemicals, electronic conduction in the electrolyte can reduce the number of oxygen ion transfers, thereby making it impractical to operate ceria-based electrolytes in electrolytic mode due to their lower faradaic efficiency.

[0006] Embodiments of the disclosed subject matter may address, among other things, one or more of the problems and shortcomings set forth above. [Means for solving the problem]

[0007] Embodiments of the disclosed subject matter provide high-performance solid oxide batteries by appropriately configuring one or more porous layers on the oxygen side of a non-porous oxide layer (also referred to herein as a dense electrolyte layer, or DEL). In some embodiments, the one or more porous layers can function as an electrode (e.g., a cathode in a SOFC mode), for example, by infiltration with one or more electrocatalysts. In some embodiments, sintering of the one or more porous layers and subsequent electrocatalyst infiltration are performed at a temperature below a first threshold (e.g., 1000° C.) to achieve minimal, or at least reduced, area specific resistance (ASR). Alternatively or additionally, in some embodiments, electrocatalyst infiltration and / or subsequent operation of the SOC are performed at a temperature below a second threshold (e.g., 650° C.) to maintain the nanoscale size (e.g., average particle size≦200 nm) of the electrocatalysts, thereby enabling fast oxygen transport while providing an electronically connected network that facilitates the electrochemical reaction.

[0008] In some embodiments, the one or more porous layers are porous functional layers (PFLs) disposed between the non-porous oxide layer and the air-side electrode. In some embodiments, the PFL can increase the exposure of the non-porous oxide layer to higher oxygen partial pressures (pO2), thereby limiting the electronic conductivity of the non-porous oxide layer and mitigating any leakage current therein. The provision of a PFL increases the effective ion transfer number t o2- can be increased, further improving the efficiency of the non-porous oxide layer, and / or a thinner non-porous oxide layer can be used. In some embodiments, the SOC with a PFL can exhibit a higher open circuit voltage (e.g., at least 0.90 V at a temperature in the range of 500-550° C.) and / or a lower ASR.

[0009] In one or more embodiments, the solid oxide battery can include a non-porous oxide layer, one or more first porous layers, and one or more second porous layers. The non-porous oxide layer can be configured to conduct oxygen ions and operate as a solid electrolyte. The one or more first porous layers can be disposed on a first face of the non-porous oxide layer. The one or more second porous layers can be disposed on a second side of the non-porous oxide layer opposite the first side. The non-porous oxide layer can have a density greater than the density of each of the first and second porous layers. The electronic conductivity of the non-porous oxide layer can be less than 25% of the ionic conductivity of the non-porous oxide layer. For each of the first and second porous layers, the electronic conductivity of the respective porous layer can be greater than 25% of the ionic conductivity of the respective porous layer. At least one of the one or more first porous layers can be configured to operate as a first electrode, and at least one of the one or more second porous layers can be configured to operate as a second electrode.

[0010] In one or more embodiments, the solid oxide battery can include a non-porous oxide layer, a porous functional layer, one or more first porous layers, and one or more second porous layers. The non-porous oxide layer can be configured to conduct oxygen ions and operate as a solid electrolyte. The porous functional layer can be disposed on a first surface of the non-porous oxide layer. The one or more first porous layers can be disposed on a surface of the porous functional layer opposite the non-porous oxide layer. The one or more second porous layers can be disposed on a second side of the non-porous oxide layer opposite the first side. The non-porous oxide layer can have a density greater than the density of the porous functional layer. The electronic conductivity of the non-porous oxide layer can be less than 25% of the ionic conductivity of the non-porous oxide layer. The porous functional layer is effective to provide an ion migration number of the non-porous oxide layer and the porous functional layer of 0.9 or greater at or below 550° C. At least one of the one or more first porous layers can be configured to operate as a first electrode, and at least one of the one or more second porous layers can be configured to operate as a second electrode.

[0011] In one or more embodiments, a method of manufacturing a solid oxide battery can include providing one or more first precursors for forming one or more second porous layers. The method can further include providing one or more second precursors for forming a non-porous oxide layer on the one or more first precursors. The method can also include sintering the first and second precursors at a temperature equal to or greater than a first threshold to form one or more second porous layers on a second side of the non-porous oxide layer. The method can further include providing one or more third precursors for forming one or more first porous layers on a first side of the non-porous oxide layer opposite the second side. The method can also include sintering the one or more third precursors at a temperature less than a first threshold to form one or more first porous layers on the first side of the non-porous oxide layer. The non-porous oxide layer can have a density greater than the density of the first and second porous layers. For each of the first and second porous layers, the electronic conductivity of the respective porous layer can be greater than 25% of the ionic conductivity of the respective porous layer. At least one of the one or more first porous layers can be configured to act as a first electrode, and at least one of the one or more second porous layers can be configured to act as a second electrode.

[0012] In one or more embodiments, a method of manufacturing a solid oxide battery can include providing one or more first precursors for forming one or more second porous layers. The method can further include providing one or more second precursors for forming a non-porous oxide layer on the one or more first precursors. The method can also include sintering the first and second precursors at a temperature equal to or greater than a first threshold to form one or more second porous layers on a second side of the non-porous oxide layer. The method can further include providing one or more third precursors for forming a porous functional layer on a first side of the non-porous oxide layer opposite the second side. The method can also include providing one or more fourth precursors for forming one or more first porous layers on the one or more third precursors. The method can further include sintering the third and fourth precursors at a temperature less than a first threshold to form a porous functional layer on the first side of the non-porous oxide layer and to form one or more first porous layers on a side of the porous functional layer opposite the non-porous oxide layer. The non-porous oxide layer may have a density greater than the density of the first and second porous layers. For each of the first and second porous layers, the electronic conductivity of the respective porous layer may be greater than 25% of the ionic conductivity of the respective porous layer. The porous functional layer is effective to cause the ionic mobility number of the non-porous oxide layer and the porous functional layer to be greater than or equal to 0.9 at or below 550° C. At least one of the one or more first porous layers may be configured to operate as a first electrode and at least one of the one or more second porous layers may be configured to operate as a second electrode.

[0013] Any of the various innovations of the present disclosure can be used in combination or separately. This Summary is provided to introduce in a simplified form a selection of concepts that are further described in the Detailed Description below. This Summary is not intended to identify key features or essential features of the claimed subject matter, nor is it intended to be used to limit the scope of the claimed subject matter. The foregoing and other objects, features, and advantages of the disclosed technology will become more apparent from the following Detailed Description, which proceeds with reference to the accompanying drawings. [Brief description of the drawings]

[0014] The embodiments will now be described with reference to the accompanying drawings, which are not necessarily drawn to scale. Where applicable, some elements may be simplified or otherwise not shown to help illustrate and explain the underlying features. Like reference numbers refer to like elements throughout the drawings. [Figure 1A] FIG. 1A is a schematic diagram illustrating a simplified cross-section of a layer assembly for a solid oxide electrochemical cell (SOC) having electrodes formed by infiltration of a porous layer in accordance with one or more embodiments of the disclosed subject matter. [Figure 1B] FIG. 1B illustrates an exemplary configuration of a SOC having a permeated porous layer in accordance with one or more embodiments of the disclosed subject matter. [Figure 1C] FIG. 1C shows the potential oxygen transport mechanism of the oxygen-containing gas composite electrode in a conventional SOC. [Figure 1D] FIG. 1D is a diagram illustrating a potential oxygen transport mechanism for an electrode formed by a permeated porous layer in accordance with one or more embodiments of the disclosed subject matter. [Figure 2A] FIG. 2A is a schematic diagram illustrating a simplified cross-section of a layer assembly for a solid oxide electrochemical cell (SOC) having a porous functional layer in accordance with one or more embodiments of the disclosed subject matter. [Figure 2B]FIG. 2B illustrates an exemplary configuration of a SOC having a porous functional layer, as well as a scanning electron microscope (SEM) image of the fabricated porous functional layer microstructure, in accordance with one or more embodiments of the disclosed subject matter. [Figure 2C] FIG. 2C shows the theoretical electronic charge carrier density versus cross-sectional position for the SOC with and without a porous functional layer. [Figure 2D] FIG. 2D shows the theoretical ratio of ionic conductivity to total conductivity (tO2-) versus cross-sectional position for SOC with and without a porous functional layer. [Figure 3A-3B] 3A-3B are simplified schematic diagrams of a SOC having a porous layer operating in fuel cell mode and electrolyzer mode, respectively, in accordance with one or more embodiments of the disclosed subject matter. [Figure 3C] FIG. 3C depicts a generalized example of a computing environment in which the disclosed technology can be implemented. [Figure 4] FIG. 4 is a process flow diagram illustrating a simplified method for manufacturing a SOC having a porous layer in accordance with one or more embodiments of the disclosed subject matter. [Figure 3A] FIG. 5A is a Nyquist plot of the open circuit voltage at 550° C. of the fabricated symmetric cell having a Pr—Sr—Co (PSC) infiltrated porous layer for various temperatures for sintering the porous layer. [Figure 5B] FIG. 5B is a graph of area specific resistance (ASR) of cathodes formed by infiltrated porous layers at different operating temperatures as a function of temperature for sintering the porous layer (X-axis). [Figure 5C] FIG. 5C shows the distribution of relaxation time (DRT) analysis at 550 °C for the conventional composite cathode (SSC-GDC) and the infiltrated porous layer cathode (PSC-infiltrated GDC). [Figure 6A-6B] 6A-6B show the current-voltage characteristics and electrochemical impedance spectroscopy (EIS) spectra for various components of the porous layer and electrocatalyst loading of the SOC with a permeated porous layer cathode in air and anode in 97% H2 / 3% H2O at 550 °C, respectively. [Figure 6C] FIG. 6C is a graph of ohmic resistance versus lanthanide loading for the SOC with a porous layer cathode. [Figure 6D] FIG. 6D is a graph of the ASR and peak power density (PPD) of the SOC with an infiltrated porous 5 wt % Pr-GDC layer cathode based on PSC loading. [Figure 7A-7B] 7A-7B show the current-voltage characteristics and E-IS spectra, respectively, for SOCs with PSC-infiltrated Pr-Sm-GDC porous layer, Ni-GDC anode, and cathode formed by various GDC electrolyte thicknesses in H2 at 500 °C and 550 °C. [Figure 7C-7D] 7C-7D are scanning electron microscope (SEM) images of the full cross section and cathode, respectively, of a SOC with a PSC-infiltrated Pr-Sm-GDC porous layer, a Ni-GDC anode, and a 20 μm-thick GDC electrolyte after aging at 550 °C for 500 h. [Figure 7E] FIG. 7E shows the long-term galvanostatic (0.2 A / cm) stability and induced PPD of a SOC with a PSC-infiltrated Pr-Sm-GDC porous layer, a Ni-GDC anode, and a 20 μm-thick GDC electrolyte at 550 °C. [Figure 7F] FIG. 7F shows the full ohmic and deconvoluted electrode ASR over time for a SOC with a PSC-infiltrated Pr-Sm-GDC porous layer, a Ni-GDC anode, and a 20 μm-thick GDC electrolyte after aging at 550 °C for 500 h. [Figure 8A] FIG. 8A shows EIS spectra in OCV for various operating temperatures for a SOC with PSC-infiltrated 5Pr-5Sm-90GDC with 10 wt % PMMA, a Ni-GDC anode, and a 10 μm-thick GDC electrolyte with pO2=1 atm on the cathode side. [Figure 8B]FIG. 8B shows the deconvoluted impedance values ​​at open circuit voltage (OCV) over various temperatures for a SOC with 10 wt % PMMA, a Ni-GDC anode, and a PSC-infiltrated 5Pr-5Sm-90GDC with a 10 μm thick GDC electrolyte, with 100 standard cubic centimeters per minute (sccm) O and 100 sccm H flowing to the cathode and anode, respectively. [Figure 8C] FIG. 8C shows the current-voltage characteristics of an SOC with PSC-infiltrated 5Pr-5Sm-90GDC with 10 wt % PMMA, Ni-GDC anode, and 10 μm-thick GDC electrolyte at different operating temperatures. [Figure 8D] FIG. 8D shows the current response of SOC during potentiostatic aging at 0.75 V and cyclic measurements of open circuit voltage (OCV) using PSC-infiltrated 5Pr-5Sm-90GDC with 10 wt % PMMA, Ni-GDC anode, and 10 μm thick GDC electrolyte at 600 °C. [Figure 9A] FIG. 9A shows Arrhenius plots of non-ohmic ASR for substitution of Sr in Pr-Sr-Co infiltrate (Pr-X-Co) of 5Pr-5Sm-90GDC porous layer with 10 wt % PMMA in a symmetric cell, as well as a LSCF-GDC composite cathode in a symmetric cell for reference. [Figure 9B] FIG. 9B is an Arrhenius plot of non-ohmic ASR for substitution of Co in Pr-Sr-Co infiltration (Pr-Sr-X) of 5Pr-5Sm-90GDC porous layer with 10 wt % PMMA in a symmetric cell, as well as a LSCF-GDC composite cathode for reference. [Figure 9C] FIG. 9C shows ASR aging for substitution of Sr in Pr-Sr-Co infiltration (Pr-X-Co) of a 5Pr-5Sm-90GDC porous layer with 10 wt % PMMA in a symmetric cell. [Figure 9D] FIG. 9D shows ASR aging for substitution of Co in Pr-Sr-Co infiltration (Pr-Sr-X) of 5Pr-5Sm-90GDC porous layer with 10 wt % PMMA in a symmetric cell. [Figure 10A-10B]10A-10B show current-voltage characteristics at 550° C. and 500° C. of an SOC with a 5Pr-5Sm-90GDC porous membrane cathode, a Ni-GDC anode, and a 20 μm thick GDC electrolyte. [Fig. 10C-10D] 10C-10D show EIS spectra at 550° C. and 500° C., respectively, for 5Pr-5Sm-90GDC porous layer cathodes with various porosities, Ni-GDC anodes, and SOCs with 20 μm-thick GDC electrolyte. [Figure 10E] FIG. 10E shows the PPD as a function of porosity calculated for a SOC with a 5Pr-5Sm-90GDC porous layer cathode, a Ni-GDC anode, and a 20 μm thick GDC electrolyte. [Fig. 10F-10G] Figures 10F-10G show the deconvoluted ASR at 500 °C and 550 °C as a function of porosity calculated for SOC with a 5Pr-5Sm-90GDC porous layer cathode, a Ni-GDC anode, and a 20 μm-thick GDC electrolyte, respectively. [Figure 11A] FIG. 11A is an SEM image of a cross section of a porous functional layer in the fabricated SOC. [Figure 11B] FIG. 11B shows the current-voltage characteristics of the SOC with and without a porous functional layer at 500° C. and 550° C. [Figure 11C] FIG. 11C shows the SOC with and without porous functional groups at 550° C. [Figure 11D] FIG. 11D shows the E-IS spectra of SOC with and without porous functional groups at 500° C. [Figure 12A] FIG. 12A shows the ion migration number versus operating temperature for a 200 μm GDC layer with and without a 10 μm porous functional layer. [Figure 12B]FIG. 12B shows the open circuit voltage (OCV) versus operating temperature for SOCs with a 20 μm GDC layer and different thicknesses of porous functional layer (PFL) compared to SOCs with 20 or 200 μm dense GDC layers and no PFL, illustrating the approach to OCV for various electrolyte ion transfer numbers. [Figure 12C] FIG. 12C shows the ohmic resistance and OCV at 500° C. and 600° C. for various thicknesses of GDC electrolyte layer paired with a 10 μm porous functional layer (with 0.5 wt % PrO2-x). [Figure 12D] FIG. 12D shows the OCV versus temperature for different Pr doping levels in a 10 μm porous functional layer on a 10 μm dense electrolyte layer, and how each approaches the OCV for various electrolyte ion migration numbers. [Figure 13A] FIG. 13A is a Nyquist plot of the SSC-GDC cathode symmetric cell with a porous functional layer with varying Pr doping levels at 500° C. [Figure 13B] FIG. 13B shows the Arrhenius behavior of a symmetric cell with only a porous functional layer. [Figure 13C] FIG. 13C shows the Arrhenius behavior of the SSC-GDC symmetric cell with and without the porous functional layer. [Figure 13D] FIG. 13D shows the DRT analysis of the SSC-GDC cathode symmetric cell with porous functional layers with varying Pr doping levels at 500° C. [Figure 13E] FIG. 13E shows the oxygen partial pressure (pO2) dependent behavior comparing the SSC-GDC cathode layer with and without the porous functional layer at 500 °C. [Figure 13F] FIG. 13F shows the DRT analysis of the SSC-GDC cathode layer without and with a porous functional layer. [Figure 14A-14B]14A-14B show the current-voltage characteristics and EIS spectra of an SOFC with a Pr-surface-modified (SM) SSC-GDC cathode, a porous functional layer, a GDC electrolyte layer, and a Ni-GDC anode, and an SOFC with a SSC-GDC cathode, a porous functional layer, a GDC electrolyte layer, and a Ni-GDC anode, respectively, at 500°C. [Figure 14C] FIG. 14C shows galvanostatic and PPD aging results for a SOFC with a Pr surface-modified (SM) SSC-GDC cathode, a porous functional layer, a GDC electrolyte layer, and a Ni-GDC anode at 500° C., and a SOFC with a SSC-GDC cathode, a porous functional layer, a GDC electrolyte layer, and a Ni-GDC anode at 550° C. [Figure 14D] FIG. 14D shows the ASR change over time for a SOFC with a Pr surface-modified (SM) SSC-GDC cathode, a porous functional layer, a GDC electrolyte layer, and a Ni-GDC anode at 500° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] General Considerations For purposes of this specification, certain aspects, advantages, and novel features of the disclosed embodiments are described herein. The disclosed methods and systems should not be construed as limiting in any way. Instead, the disclosure is directed to all novel and non-obvious features and aspects of the various disclosed embodiments, both alone and in various combinations and subcombinations with each other. The methods and systems are not limited to any particular aspects, features, or combinations thereof, and the disclosed embodiments do not require that any one or more particular advantages exist or problems be solved. Techniques from any embodiment or example can be combined with techniques described in any one or more of the other embodiments or examples. In view of the many possible embodiments to which the principles of the disclosed technology may be applied, it should be recognized that the illustrated embodiments are merely illustrative and should not be construed as limiting the scope of the disclosed technology.

[0016] Although some operations of the disclosed methods are described in a particular order for convenient presentation, it should be understood that this method of description encompasses reordering, unless a particular ordering is required by the specific language described below. For example, operations described in sequence may in some cases be reordered or performed simultaneously. Furthermore, for simplicity, the accompanying drawings may not show the various ways in which the disclosed methods may be used in conjunction with other methods. Furthermore, the description may use terms such as "provide" or "achieve" to describe the disclosed methods. These terms are high-level abstractions of the actual operations that are performed. The actual operations that correspond to these terms may vary depending on the particular implementation and are readily discernible by those skilled in the art.

[0017] Disclosure of numerical ranges should be understood to refer to each discrete point within the range, including the endpoints, unless otherwise indicated. Unless otherwise indicated, all numbers expressing amounts of ingredients, molecular weights, percentages, temperatures, times, and the like used in this specification or claims should be understood to be modified by the term "about". Thus, unless otherwise implicitly or explicitly indicated, or unless the context is properly understood by those skilled in the art to have a clearer configuration, the numerical parameters described are approximations that may depend on the desired properties sought and / or the limits of detection under standard test conditions / methods, as known to those skilled in the art. Whenever the embodiment numbers are directly and explicitly distinguished from the prior art discussed, the embodiment numbers are not approximations unless the word "about" is recited. Whenever "substantially", "approximately", "about", or similar language is explicitly used in conjunction with a particular value, a variation of up to 10% of that value is intended, unless explicitly stated otherwise.

[0018] Directions and other relative references may be used to facilitate the description of the figures and principles herein, but are not intended to be limiting. For example, certain terms such as "inside," "outside," "up," "down," "top," "bottom," "internal," "external," "left," "right," "front," "rear," "rearward," and the like may be used. Such terms are used, where applicable, to provide some clarity of description when dealing with relative relationships, particularly with respect to the illustrated embodiments. However, such terms are not intended to imply absolute relationships, positions, and / or orientations. For example, with respect to an object, a "top" portion may become a "bottom" portion by simply flipping the object over. Nevertheless, it is still the same portion, and the object remains the same.

[0019] As used herein, "comprising" means "including," and the singular forms "a" or "an" or "the" include plural references unless the context clearly dictates otherwise. The term "or" refers to a single element or a combination of two or more elements of the referenced alternative elements, unless the context clearly dictates otherwise.

[0020] The various components, parameters, operating conditions, and the like described herein may be alternatives, but these alternatives are not necessarily equivalent and / or will function equally well. Nor is it meant to imply that the options are listed in order of preference, unless otherwise indicated. Any of the groups defined below may be substituted or unsubstituted, unless otherwise indicated.

[0021] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs.Methods and materials similar or equivalent to those described herein can be used in the practice or testing of this disclosure, but suitable methods and materials are described below.The materials, methods, and examples are illustrative only and are not intended to be limiting.Features of the subject matter of this disclosure will become apparent from the following detailed description and the appended claims.

[0022] Introduction Disclosed herein are improved performance SOCs and methods for their manufacture. In some embodiments, a multi-phase electrocatalyst can be infiltrated into the porous layer on the air side (e.g., oxygen side) of the solid electrolyte to function as an air-side electrode. By proper control of the manufacturing process, improved performance SOCs can be achieved. For example, in some embodiments, the air-side porous layer (configured as an air-side electrode, such as the cathode of a SOFC) is sintered below a first threshold temperature (e.g., 1000° C.) and / or above a second threshold temperature (e.g., 900° C.) to achieve minimal ASR. Alternatively or additionally, in some embodiments, the air-side porous layer can be infiltrated with one or more electrocatalysts, whose sintering and operating temperatures are kept below 650° C., thereby maintaining nanoscale sizes that maintain high activity and durability. Alternatively or additionally, in some embodiments, one or more additives (e.g., lanthanides at a total loading of 10 wt. % or less) can be introduced during manufacture of the air-side porous layer (e.g., mixed with the precursor prior to sintering) to increase electronic conductivity, reduce ohmic losses, and / or increase PPD.

[0023] For example, FIGS. 1A-1B show a SOC 110 having at least one first porous layer 112 (e.g., functioning as an air-side electrode), a non-porous oxide layer 102 (also referred to herein as a dense electrolyte layer or DEL), and one or more second porous layers 104 (e.g., functioning as a fuel-side electrode). The first porous layer 112 can be formed to function as an electrode by infiltrating the porous scaffold 106 of the sintered layer assembly 100 with one or more electrocatalyst oxides 108 (e.g., multi-phase electrocatalysts). In some embodiments, the first porous layer 112 can have a thickness of 20 μm or less, e.g., in the range of 10-20 μm. In the illustrated example of FIG. 1A, a pair of second porous layers is illustrated, namely, a support layer 104b (e.g., an anode support layer) and a functional layer 104a (e.g., an anode functional layer). In some embodiments, the combined thickness of the one or more second porous layers 104a, 104b can be at least 300 μm. Although four layers are shown in FIG. 1A, fewer or additional layers are possible according to one or more contemplated embodiments.

[0024] The non-porous oxide layer 102 can operate as a solid electrolyte by conducting oxygen ions but without substantial conduction of electrons therethrough. For example, the electronic conductivity of the non-porous oxide layer can be less than 25% of the ionic conductivity of the non-porous oxide layer. In some embodiments, the non-porous oxide layer can have a density greater than the density of each of the first and second porous layers. Alternatively or additionally, each of the first and second porous layers can have an electronic conductivity greater than 25% of the ionic conductivity of the respective porous layer. For example, each of the first and second porous layers can have both high ionic conductivity and high electronic conductivity.

[0025] 1C-1D show a two-step oxygen transport mechanism for a composite electrode and an electrocatalyst-permeated electrode, respectively. In the composite electrode configuration 120 of FIG. 1C, dissociative adsorption 128 of oxygen 126 occurs on the surface of the first component 122 (e.g., SSC) but requires a long transport distance to the active sites 130 (e.g., GDC) on the second component 124. The long transport distance can limit the number of active sites. In contrast, in the permeated porous layer configuration 140 of FIG. 1D, the nanoscale electrocatalyst 142 (e.g., PSC) provides a larger number of active sites 144 for oxygen surface exchange, as well as a shorter diffusion length between the nanoscale electrocatalyst 142 and the nearby scaffolding 124, resulting in an associated reduction in energy losses.

[0026] In some embodiments, at least one first porous layer 112 (e.g., the porous scaffold 106) can be formed of ceria or bismuth oxide. For example, the first porous layer 112 can be formed of doped ceria, cubic bismuth oxide, rhombohedral bismuth oxide, or doped rhombohedral bismuth oxide. In some embodiments, the material composition of the first porous layer 112 is one of gadolinia-doped ceria (GDC), samaria-doped ceria (SDC), samaria-neodymium-doped ceria (SNDC), erbia-stabilized bismuth oxide (ESB), dysprosium-tungsten-stabilized bismuth oxide (DWSB), or yttria-stabilized bismuth oxide (YSB). Alternatively, in some embodiments, the first porous layer 112 comprises one of the rhombohedral bismuth oxide materials disclosed in U.S. Patent Application Publication No. 2020 / 0036028, entitled "Stable Highly Conductive Oxide Electrolytes," published January 30, 2020, which are incorporated herein by reference. For example, the rhombohedral bismuth oxide can be selected from the group consisting of LaY-Bi2O3, LaSm-Bi2O3, SrY-Bi2O3, Nd-Bi2O3, LaEr-Bi2O3, NdDy-Bi2O3, Nd-Bi2O3, Sm-Bi2O3, NdSm-Bi2O3, NdGd-Bi2O3, and CaGd-Bi2O3.

[0027] In some embodiments, at least one first porous layer 112 (e.g., the porous scaffold 106) may be formed of doped ceria doped with one or more lanthanides. For example, the one or more lanthanides added may be praseodymium, samarium, or both praseodymium and samarium. In some embodiments, the total amount of lanthanide additions may range from about 0% to about 20% by weight, such as from about 0.5% to about 10% by weight. In some embodiments, each lanthanide addition may be about 5% by weight. In some embodiments, the amount of lanthanide addition may be about 10% by weight or less of the total metal content, in which case the total amount of ceria may be at least 90% by weight.

[0028] In some embodiments, at least one first porous layer 112 (e.g., the porous scaffold 106) may be a composite material formed from (i) ceria or bismuth oxide having one or more electronically conductive and electrocatalytic oxides. Alternatively or additionally, in some embodiments, at least one first porous layer 112 (e.g., the porous scaffold 106) may be a composite material formed from lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt ferrite (LSCF), yttria stabilized zirconia (YSZ), scansia stabilized zirconia (SSZ), gadolinia doped ceria (GDC), samaria doped ceria (SDC), samaria neodymium doped ceria (SNDC), erbia stabilized bismuth oxide (EBSO), bismuth oxide (B ... bismuth oxide (ESB), dysprosium tungsten stabilized bismuth oxide (DWSB), yttria stabilized bismuth oxide (YSB), rhombohedral bismuth oxide, strontium and magnesium doped lanthanum gallate (LSGM), strontium samarium cobalt iron oxide (SSC), barium strontium cobalt iron oxide (BSCF), samarium strontium cobalt iron oxide (SSCF), lanthanum strontium manganate (LSM), and Ln2NiO 4+δ The nickelate is one or more materials selected from the group consisting of nickelates, where Ln is a lanthanide.

[0029] In some embodiments, the electrocatalyst 108 for infiltration of the porous scaffold 106 can include one or more electrocatalyst oxides. For example, the one or more electrocatalyst oxides can include one or more MOx, where M is a cation such as, but not limited to, Pr, Ca, Sr, Y, La, Nd, Sm, Dy, Er, Mn, Fe, Co, Ni, Cu, and Zn. In some embodiments, the infiltration of the electrocatalyst 108 into the porous scaffold 106 is about 60 μmol / cm or less of active area, e.g., about 9 μmol / cm or less. 2 ~About 58 μmol / cm 2 Alternatively or additionally, solution-based loading of the electrocatalyst can provide a loading of 60 μL / cm 2 The loading can be, for example, from about 19 μL / cm to about 58 μL / cm or less. The loading can depend on the composition of the electrocatalyst as well as the thickness of the porous scaffold, and thus, in some embodiments, other loading ranges may be applicable.

[0030] In some embodiments, the electrocatalyst can include at least A and B. In some embodiments, the molar ratio of A:B in the electrocatalyst can be about 1:1. In some embodiments, A can be a Group 2 element, a Group 3 element, or a lanthanide. Alternatively or additionally, in some embodiments, A can be selected from the group consisting of Pr, Ca, Sr, Y, La, Nd, Sm, Dy, and Er. In some embodiments, B can be a period 4 element. Alternatively or additionally, in some embodiments, B can be selected from the group consisting of Mn, Fe, Co, Ni, Cu, and Zn.

[0031] Alternatively or additionally, in some embodiments, the electrocatalyst can include at least Pr, A, and B. In some embodiments, the molar ratio of Pr:A:B in the electrocatalyst can be about 1:1:2. In some embodiments, A can be a Group 2 element, a Group 3 element, or a lanthanide other than Pr. Alternatively or additionally, in some embodiments, A can be selected from the group consisting of Ca, Sr, Y, La, Nd, Sm, Dy, and Er. In some embodiments, B can be a period 4 element. Alternatively or additionally, in some embodiments, B can be selected from the group consisting of Mn, Fe, Co, Ni, Cu, and Zn.

[0032] In some embodiments, the non-porous oxide layer 102 can be formed from ceria, zirconia, bismuth oxide, or lanthanum gallate. In some embodiments, the non-porous oxide layer 102 can include one or more dopants and / or one or more stabilizers. For example, in some embodiments, materials that can be used for the non-porous oxide layer 102 can include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (SSZ), gadolinia-doped ceria (GDC), samaria-doped ceria (SDC), samaria-doped neodymium-doped ceria (SNDC), erbia-stabilized bismuth oxide (ESB), yttria-stabilized bismuth oxide (YSB), rhombohedral bismuth oxide, strontium- and magnesium-doped lanthanum gallate (LSGM), and combinations thereof. In some embodiments, the non-porous oxide layer 102 is formed from the same material as the porous scaffold 106, for example, GDC.

[0033] In some embodiments, the one or more second porous layers 104 (e.g., the support layer 104b and / or the functional layer 104a) can be formed from a mixed ionic electronically conductive oxide (MIEC), such as, but not limited to, nickel cermet of ceria, nickel cermet of zirconia, nickel cermet of ceria, nickel cermet of zirconia, nickel cermet of gallate, molybdate, nickel cermet of molybdate, chromate, nickel cermet of chromate, vanadate, or nickel cermet of vanadate. In some embodiments, the one or more second porous layers 104 can include one of the chromate-based oxide materials disclosed in U.S. Pat. No. 11,228,039, entitled "Chromate-Based Ceramic Anode Materials for Solid Oxide Fuel Cells," published Jan. 18, 2022, which are incorporated herein by reference. For example, the chromate-based oxide can be Y 0.7 Ca 0.3 Cr 0.8 Cu 0.2 O 3?δ , Nd 0.7 Ca 0.3 Cr 0.8 Cu 0.2 O 3?δ , (Y 0.5 Nd 0.5 ) 0.7 Ca 0.3 Cr 0.8 Cu 0.2 O 3?δ ,Pr 0.7 Ca 0.3 Cr 0.8 Cu 0.2 O 3?δ , and La 0.6 Sr 0.4 Cr 0.9 Mo 0.1 O 3?δIn some embodiments, the one or more second porous layers 104 can include one of the strontium iron cobalt molybdenum oxide (SFCM) materials disclosed in U.S. Pat. No. 10,938,052, entitled "Alternative Anode Materials for Solid Oxide Fuel Cells," published March 2, 2021, which is incorporated herein by reference. For example, the SFCM material can be SrM 1 x M 2 ((1?x) / 2) Mo ((1?x) / 2) O 3±δ where M 1 and M. 2 is a variety of different transition metals, but is not Mo, x is about 0.1-0.5, and δ is about 0-1.5. For example, in some embodiments, M 1 is Fe, and M 2 is Co.

[0034] In some embodiments, improved SOC can be obtained by providing a porous functional layer (PFL) between the air electrode and the solid electrolyte. In some embodiments, the PFL can increase the exposure of the non-porous oxide layer to higher oxygen partial pressures (pO2), thereby limiting the electronic conductivity of the non-porous oxide layer, mitigating any leakage current therein, and / or increasing the effective ion transport number t O2- can be increased.

[0035] For example, FIGS. 2A-2B show a SOC 200 having at least one first porous layer 204 (e.g., functioning as an air-side electrode), a PFL 206, a non-porous oxide layer 202 (also referred to as a DEL), and one or more second porous layers 104 (e.g., functioning as a fuel-side electrode). In some embodiments, the PFL 206 is disposed between and in direct contact with the non-porous oxide layer 202 and the first porous layer 204. In some embodiments, the PFL 206 can have a thickness of 20 μm or less, e.g., in a range of 10-20 μm. Alternatively or additionally, in some embodiments, the non-porous oxide layer 202 can have a thickness of 20 μm or less, e.g., in a range of 10-20 μm. Alternatively or additionally, in some embodiments, the combined thickness of the PFL 206 and the non-porous oxide layer 202 can be 40 μm or less. In the illustrated example of FIG. 2A, a pair of second porous layers are shown: a support layer 104b (e.g., an anode support layer) and a functional layer 104a (e.g., an anode functional layer). In some embodiments, the total thickness of the one or more second porous layers 104a, 104b may be at least 300 μm. In some embodiments, the material composition for the one or more second porous layers 104 may be similar to that described above with respect to the SOC 110 of FIGS. 1A-1C. Although five layers are shown in FIG. 2A, fewer or additional layers are possible according to one or more contemplated embodiments.

[0036] Similar to the non-porous oxide layer 102 of FIG. 1A, the non-porous oxide layer 202 of the SOC 200 can operate as a solid electrolyte by conducting oxygen ions therethrough but not substantially conducting electrons therethrough. For example, the electronic conductivity of the non-porous oxide layer 202 can be less than 25% of the ionic conductivity of the non-porous oxide layer. In some embodiments, each of the first and second porous layers can have an electronic conductivity that is greater than 25% of the ionic conductivity of the respective porous layer. For example, the first and second porous layers 204 and 104 can have high ionic conductivity and high electronic conductivity.

[0037] In some embodiments, the non-porous oxide layer 202 can have a density greater than the density of the PFL 206. In some embodiments, the PFL 206 can be effective to increase the ion transfer number of the non-porous oxide layer 202 and the PFL 206, for example, to at least 0.9 at temperatures up to 550° C. In some embodiments, the PFL 206 can increase the open circuit voltage (OCV) of the SOC 200 and / or decrease the impedance of the SOC 200. For example, in some embodiments, a SOC 200 incorporating the PFL 206 can have an OCV of at least 0.90 V at 500-550° C.

[0038] Ce(Gd)O 2-x In the case of materials such as doped ceria, the dominant defects are controlled by the oxygen concentration, x. These defects are the main charge carriers that determine the electronic and ionic conductivity. Under reducing conditions, Ce 4+ Ce 3+ Reduction to significantly increases the electronic conductivity. From a solid-state chemistry perspective, as pO2 decreases, the electronic charge carrier concentration n increases with x to accommodate the formation of positively charged oxygen vacancies. In contrast, in the high pO2 regime, the high oxygen chemical potential maintains a low level of x, thus limiting the electronic conductivity of doped ceria.

[0039] 2C-2D show the theoretical electron charge carrier density and t versus distance for SOC200 with PFL206 and SOC210 without PFL. O2-, and the area under each curve represents the relative electronic charge carrier concentration and average migration number in the electrolyte, respectively. For SOC200, oxygen molecules can freely diffuse through the pores to achieve a uniform pO2 (and thus stoichiometry) of the PFL. Thus, the entire PFL has a constant defect concentration as it is exposed to the same environment (e.g., pO2 = 0.21 atm). In other words, the porous design of the PFL pins the oxygen chemical potential at the PFL-DEL interface to equilibrate with the oxygen gas partial pressure, thereby limiting reduction (e.g., Ce reduction).

[0040] In contrast, with only the non-porous oxide layer 102 (DEL), the oxygen gas environment extends only to the cathode / electrolyte interface. In the case of the SOC 200 with the PFL 206, the oxygen chemical potential boundary condition of the cathode gas environment can extend from the cathode / electrolyte interface to the DEL / PFL interface due to the porous nature of the PFL. This change provides an extended electrolytic region with significantly lower electronic charge carrier density, as shown in FIG. 2C. As a result, the effective value t O2- This enhancement in the ionic / electronic conductivity ratio can significantly improve the efficiency of non-porous oxide layers (e.g., ceria-based electrolytes). Furthermore, because the PFL extends the cathode pO2 throughout its structure, it is possible to achieve high concentrations of Pr in this structure without the negative impact on ionic conductivity of having Pr on the low pO2 side of the dense electrolyte. O2- This provides an opportunity to utilize Pr-doped ceria.

[0041] In some embodiments, the non-porous oxide layer 202 can be formed of ceria or bismuth oxide. In some embodiments, the non-porous oxide layer 202 can include one or more dopants and / or one or more stabilizers. For example, in some embodiments, materials that can be used for the non-porous oxide layer 202 can include, but are not limited to, GDC, samaria doped ceria SDC, samaria neodymium doped ceria SNDC, erbia stabilized bismuth oxide ESB, yttria stabilized bismuth oxide YSB, rhombohedral bismuth oxide, and combinations thereof. In some embodiments, the non-porous oxide layer 202 is formed of the same material as the PFL 206, for example, GDC.

[0042] In some embodiments, at least one first porous layer 204 may be a composite material formed of (i) ceria or bismuth oxide and (ii) one or more electronically conductive and electrocatalytic oxides. In some embodiments, the material for the first porous layer 204 may be a composite having (1) a material selected from a first group consisting of LSCF, BSCF, SSCF, SSC, and LSM, and (2) a material selected from a second group consisting of YSZ, SSZ, GDC, SDC, SNCD, ESB, DWSB, YSB, rhombohedral bismuth oxide, and LSGM. For example, the first porous layer 204 may be a composite of SSC-GDC. Alternatively or additionally, in some embodiments, the at least one first porous layer 204 is made of any of the following: LSC, LSCF, YSZ, SSZ, GDC, SDC, SNDC, ESB, DWSB, YSB, rhombohedral bismuth oxide, LSGM, SSC, BSCF, SSCF, LSM, and LnNiO nickelate, where Ln is a lanthanide. 4+δ The adhesive layer may be formed from one or more materials selected from the group consisting of:

[0043] In some embodiments, at least one first porous layer 204 can be infiltrated and / or surface modified with one or more electrocatalyst oxides. For example, see Huang et al., “Nanointegrated, High-Performing Cobalt-Free Bismuth-Based Composite Cathode for Low-Temperature Solid Oxide Fuel Cells.” ACS Appl. Mater.Interfaces, 2018, 10(34): pp.28635-43. For example, one or more electrocatalyst oxides can include one or more MOx, where M is a cation such as, but not limited to, Pr, Ca, Sr, Y, La, Nd, Sm, Dy, Er, Mn, Fe, Co, Ni, Cu, and Zn.

[0044] Although specific materials and configurations have been discussed above and elsewhere herein, embodiments of the disclosed subject matter are not limited thereto. Rather, in accordance with one or more contemplated embodiments, other functionally similar materials can be used in one or more layers of the disclosed SOC to achieve the same or similar effects.

[0045] Solid Oxide Battery System In some embodiments, the SOC 110 of FIGS. 1A-1B or the SOC 200 of FIGS. 2A-2B can operate as a solid oxide fuel cell (SOFC), the basic operation of which is described in U.S. Pat. No. 9,525,179, entitled "Ceramic Anode Materials for Solid Oxide Fuel Cells," published Dec. 20, 2016, and incorporated herein by reference. For example, FIG. 3A shows a SOFC system 300 that uses a SOC layer assembly 308 having a solid oxide electrolyte 302 (e.g., non-porous oxide layer 102 or 202), a fuel-side electrode 304 (anode, e.g., second porous layer 104), and an air-side electrode 306 (cathode, e.g., first porous layer 112 or 204). The SOFC system 300 can have an external circuit 322 (e.g., load) and a controller 324, for example, to control the operation of the system 300. In some embodiments, the SOFC system 300 can include a fuel storage 326 from which fuel can be distributed to generate electricity.

[0046] An input stream of air or oxygen-containing gas can flow to the air-side electrode 306 via a first port 318 of the air-side manifold 316. In some embodiments, the input stream provided to the first port 318 can have an oxygen concentration in the range of 20-100% (mole fraction). As the air passes through the electrode 306, oxygen atoms in the input stream can be reduced within the electrode 306 to produce oxygen ions that flow toward the second side 302b of the electrolyte 302. The oxygen ions migrate through the electrolyte 302 into the electrode 304 on the first side 302a of the electrolyte 302. Any unused gas can exit the manifold 316 via a second port 320.

[0047] Fuel can flow to the fuel-side electrode 304 via a first port 312 of the fuel-side manifold 310. In some embodiments, the fuel supplied to the first port 312 can include H2, CO, NH3, hydrocarbon gases derived from methane, higher hydrocarbons (such as, but not limited to, gasoline, diesel, biogas, etc.), or any combination thereof. Oxygen ions can react with the fuel at the electrode 304 to oxidize the fuel and generate electrons that flow from the fuel-side electrode 304 to the electronic circuit 322 and back to the air-side electrode 306. Oxidation products (e.g., water, carbon dioxide, etc.) and / or unused fuel can exit the manifold 310 via a second port 314.

[0048] Alternatively or additionally, in some embodiments, the SOC 200 of Figures 2A-2B can be operated as a solid oxide electrolysis cell (SOEC). For example, Figure 3B shows an SOEC system 330 that uses an SOC layer assembly 308 having a solid oxide electrolyte 302 (e.g., non-porous oxide layer 202), a fuel side electrode 304 (cathode, e.g., second porous layer 104), and an air side electrode 306 (anode, e.g., first porous layer 204). The SOEC system 300 can have an external circuit 322 (e.g., power source) and a controller 324, for example, to control the operation of the system 330. In some embodiments, the SOFC system 330 can include a fuel reservoir 326 in which the generated fuel can be stored.

[0049] The reactants (e.g., H2O and / or CO2) can flow to the fuel electrode 304 via the second port 314 of the fuel manifold 310. Electrons from the external circuit 322 can be used to reduce the reactants in the electrode 304, thereby producing oxygen ions that flow toward the first side 302a of the electrolyte 302, as well as fuel (e.g., H2, CO, etc.). The reaction products and any used reactants can be directed to a fuel reservoir 326 via the first port 312 of the manifold 310 for later use. Meanwhile, the oxygen ions can travel through the electrolyte 302 to the electrode 306 on the second side 302b, where they are converted to oxygen molecules, where they can be exhausted from the manifold 316 via air flowing through the first port 318.

[0050] Alternatively or additionally, in some embodiments, the SOC can operate reversibly, e.g., operating as a SOFC300 in a first operating mode (e.g., to generate electricity from a fuel) and reversing the polarity (e.g., of the circuit 322) to operate as a SOEC330 in a second operating mode (e.g., to store energy in the fuel).

[0051] Fabrication of solid oxide batteries FIG. 4 illustrates an exemplary method 400 for manufacturing an SOC, such as SOC 110 of FIGS. 1A-1B or SOC 200 of FIGS. 2A-2B. Method 400 can begin with process step 402, where one or more first precursors are provided to form one or more second porous layers (e.g., fuel-side porous layers, such as layers 104a and / or 104b of FIGS. 1A or 2A). In some embodiments, providing process step 402 can include tape casting, blade coating, laminating, screen printing, or any combination thereof. The one or more first precursors can include precursors capable of forming any of the above-mentioned materials for the second porous layer upon sintering in process step 406. For example, providing process step 402 can include mixing nickel oxide and GDC in a first slurry and then tape casting to form the first precursor layer. In some embodiments, the one or more first precursors can include a pore former, e.g., PMMA particles (e.g., having a diameter of ∼1.5 μm) at a loading of 0-15 wt %, inclusive. For example, providing the treating step 402 can include mixing the pore former into the first slurry prior to tape casting.

[0052] The method 400 can proceed to process step 404, where one or more second precursors are provided to form a non-porous oxide layer (e.g., layer 102 of FIG. 1A or layer 202 of FIG. 2A). In some embodiments, the providing of process step 404 can include tape casting, blade coating, laminating, screen printing, or any combination thereof. The one or more second precursors can include precursors that can form any of the above-mentioned materials for the non-porous oxide layer upon sintering in process step 406. For example, the providing of process step 404 can include mixing GDC into a second slurry and then tape casting to form the second precursor layer. Since the non-porous oxide layer forms a dense layer, no pore former is provided in the second slurry. The one or more second precursors can be provided on or directly onto the previously formed first precursor layer, for example, by hot roll lamination.

[0053] The method 400 may proceed to process step 406, where the first and second precursors are sintered at an elevated temperature (e.g., above threshold T1) to form one or more second porous and non-porous oxide layers, respectively. In some embodiments, threshold T1 is about 1000° C. For example, the sintering of step 406 may be performed at about 1450° C. In some embodiments, the sintering of process step 406 may be for at least 1 hour, for example, about 4 hours.

[0054] The method 400 can proceed to a decision step 408, where it is determined whether the SOC should include a PFL. If a PFL is not desired, the method 400 can proceed to a process step 410, where one or more third precursors are provided to form one or more first porous layers (e.g., layer 106 of FIG. 1A). In some embodiments, the providing in the process step 410 can include tape casting, blade coating, laminating, screen printing, or any combination thereof. The one or more third precursors can include precursors that can form any of the above-mentioned materials for the first porous layer upon sintering in the process step 412. For example, the providing in the process step 410 can include mixing ceria (e.g., GDC) with or without a lanthanide additive (e.g., 0.5-5 wt. % praseodymium oxide and / or 0.5-5 wt. % samarium oxide) into an ink, followed by tape casting or blade coating to form the third precursor layer. In some embodiments, the one or more third precursors can include a pore-forming agent, for example PMMA particles (e.g., having a diameter of ∼1.5 μm) at a loading of 0-15 wt % (e.g., ∼5 wt % PMMA). For example, providing the treatment step 410 can include mixing the pore-forming agent into the ink prior to tape casting. In some embodiments, the one or more third precursors can be provided directly on or over a previously formed non-porous oxide layer.

[0055] Method 400 may proceed to process step 412, where the one or more third precursors may be sintered at a low temperature (e.g., below threshold T1) to form one or more first porous layers. In some embodiments, threshold T1 is about 1000° C. For example, sintering step 412 may be performed at about 950° C. In some embodiments, sintering step 412 may be for at least 1 hour, such as about 2 hours. In some embodiments, sintering step 412 may include a low temperature intermediate burnout (e.g., 400° C. for 30 minutes) to burn out the PMMA and binder.

[0056] The method 400 can proceed to process step 414, where at least one of the one or more first porous layers can be infiltrated with one or more electrocatalysts (e.g., electrocatalyst 108 of FIG. 1A) and then sintered at an even lower temperature (e.g., below a threshold T2 that is below threshold T1). The one or more electrocatalysts can include any of the materials described above for electrocatalysis. In some embodiments, the infiltration can include one or more cycles of vacuum infiltration. For example, an electrocatalyst in a solution (e.g., a nitrate solution) can be placed on the exposed surface of the first porous layer and subjected to a vacuum to promote infiltration of the solution into the pores of the layer. This can be repeated one or more times with additional solution before calcining to evaporate and / or burn off the solvent. For example, the calcination can be performed at less than 650° C., e.g., at 450° C. for 30 minutes. In some embodiments, the infiltration cycle can include at least two solution applications and vacuum repetitions followed by heating. In some embodiments, the infiltration cycle can be performed one or more times to achieve a desired electrocatalyst loading.

[0057] If it is determined that a PFL should be included in the SOC, the method 400 can proceed from the decision step 408 to a process step 416, where one or more third precursors are provided to form the PFL (e.g., layer 206 of FIG. 2A). In some embodiments, the providing in the process step 416 can include tape casting, blade coating, laminating, screen printing, or any combination thereof. The one or more third precursors can include precursors that can form any of the above-mentioned materials for the PFL upon sintering in the process step 420. For example, the providing in the process step 416 can include mixing ceria (e.g., GDC) with or without a lanthanide additive (e.g., 0.5-5 wt. % praseodymium oxide and / or 0.5-5 wt. % samarium oxide) into an ink, followed by tape casting or blade coating to form a third precursor layer. In some embodiments, the one or more third precursors can include a pore-forming agent, for example PMMA particles (e.g., having a diameter of ∼1.5 μm) at a loading of 0-15 wt % (e.g., ∼5 wt % PMMA). For example, providing the treatment step 416 can include mixing the pore-forming agent into the ink prior to tape casting. In some embodiments, the one or more third precursors can be provided directly on or over a previously formed non-porous oxide layer.

[0058] The method 400 can proceed to process step 418, where one or more fourth precursors are provided to form one or more first porous layers (e.g., an air-side porous layer such as layer 204 of FIG. 2A). In some embodiments, the providing of process step 418 can include tape casting, blade coating, laminating, screen printing, or any combination thereof. The one or more fourth precursors can include precursors that can form any of the above-mentioned materials for the first porous layer upon sintering in process step 420. For example, the first porous layer can be a composite electrode, and the providing of process step 418 can include mixing two different ceria (e.g., SSC and GDC) into an ink and then screen printing as the fourth precursor layer on or directly onto the previously formed third precursor layer. Alternatively, in some embodiments, the first porous layer can be a permeated electrode, in which case electrocatalytic infiltration (e.g., similar to process step 414) can be performed after sintering in process step 420.

[0059] Method 400 can proceed to process step 420, where the third and fourth precursors are sintered at a low temperature (e.g., below threshold T1) to form a PFL and one or more first porous layers, respectively. In some embodiments, threshold T1 is about 1000° C. For example, the sintering of step 420 can be performed at about 950° C. In some embodiments, the sintering of process step 420 can be for at least 1 hour, for example, about 2 hours.

[0060] Although steps 402-420 of method 400 have been described as being performed once, in some embodiments, multiple iterations of a particular processing step may be used before proceeding to the next decision or processing step. In addition, while steps 402-420 of method 400 have been illustrated and described separately, in some embodiments, the processing steps may be combined and performed together (concurrently or sequentially). Furthermore, while FIG. 4 illustrates a particular order of steps 402-420, embodiments of the disclosed subject matter are not limited thereto. Indeed, in certain embodiments, steps may occur in a different order than those illustrated, or simultaneously with other steps. In some embodiments, method 400 may comprise only some of steps 402-420 of FIG. 4.

[0061] Computer implementation 3C illustrates a generalized example of a suitable computing environment 331 in which the described innovations may be implemented, such as, for example, aspects of the SOC controller 324 or manufacturing method 400. The computing environment 331 is not intended to suggest any limitation as to scope of use or functionality, as the innovations may be implemented in a variety of general purpose or special purpose computing systems. For example, the computing environment 331 may be any of a variety of computing devices (e.g., a desktop computer, a laptop computer, a server computer, a tablet computer, etc.).

[0062] Referring to FIG. 3C, the computing environment 331 includes one or more processing units 335, 337 and memory 339, 341. In FIG. 3C, this basic configuration 351 is included within the dashed line. The processing units 335, 337 execute computer-executable instructions. The processing units may be a central processing unit (CPU), a processor in an application specific integrated circuit (ASIC), or any other type of processor (e.g., hardware processor, graphics processing unit (GPU), virtual processor, etc.). In a multi-processing system, the multiple processing units execute computer-executable instructions to increase processing power. For example, FIG. 3C shows a central processing unit 335 and a graphics processing unit or co-processing unit 337. The tangible memory 339, 341 may be volatile memory (e.g., registers, cache, RAM), non-volatile memory (e.g., ROM, EEPROM, flash memory, etc.), or some combination of the two accessible by the processing units. The memories 339, 341 store software 333 in the form of computer-executable instructions suitable for execution by a processing unit(s) that implements one or more of the innovations described herein.

[0063] A computing system may have additional features. For example, computing environment 331 includes storage 361, one or more input devices 371, one or more output devices 381, and one or more communication connections 391. An interconnection mechanism (not shown), such as a bus, controller, or network, interconnects the components of computing environment 331. Typically, operating system software (not shown) provides an operating environment for other software executing in computing environment 331 and coordinates the activities of the components of computing environment 331.

[0064] Tangible storage 361 may be removable or non-removable and includes magnetic disks, magnetic tapes or cassettes, CD-ROMs, DVDs, or any other medium that can be used to store information in a non-transitory manner and that can be accessed within computing environment 331. Storage 361 may store instructions for software 333 that implements one or more of the innovations described herein.

[0065] The input device(s) 371 may be a touch input device such as a keyboard, a mouse, a pen, or a trackball, a voice input device, a scanning device, or another device that provides input to the computing environment 331. The output device 371 may be a display, a printer, speakers, a CD-writer, or another device that provides output from the computing environment 331.

[0066] The communications connection(s) 391 enable communication over a communications medium to another computing entity. The communications medium conveys information such as computer-executable instructions, audio or video input or output, or other data in a modulated data signal. A modulated data signal is a signal that has one or more of its characteristics set or changed in such a manner as to encode information in the signal. By way of example, and not limitation, the communications medium may be electrical, optical, radio frequency (RF), or another carrier.

[0067] Any of the disclosed methods may be implemented as computer-executable instructions stored on one or more computer-readable storage media (e.g., one or more optical media disks, volatile memory components (such as DRAM or SRAM), or non-volatile memory components (such as flash memory or hard drives)) and executed on a computer (e.g., any commercially available computer, including a smartphone or other mobile device that includes computing hardware). The term computer-readable storage medium does not include communication connections such as signals and carrier waves. Any computer-executable instructions for implementing the disclosed techniques, as well as any data created and used during the implementation of the disclosed embodiments, may be stored on one or more computer-readable storage media. The computer-executable instructions may be part of a dedicated software application or a software application that is accessed or downloaded, for example, via a web browser or other software application (such as a remote computing application). Such software may be executed, for example, on a single local computer (e.g., any suitable commercially available computer) or in a networked environment using one or more networked computers (e.g., via the Internet, a wide area network, a local area network, a client-server network (such as a cloud computing network), or any other such network).

[0068] For clarity, only selected aspects of the software-based implementation are described. Other details that are well known in the art are omitted. For example, it should be understood that the disclosed technology is not limited to any particular computer language or program. For example, aspects of the disclosed technology may be implemented in any language, including C++, Java TM, Python, and / or any other suitable computer language. Similarly, the disclosed technology is not limited to any particular computer or hardware type. Specific details of suitable computers and hardware are well known and need not be described in detail in this disclosure.

[0069] It should also be appreciated that any functionality described herein may be performed, at least in part, by one or more hardware logic components instead of software. For example, and without limitation, exemplary types of hardware logic components that may be used include field programmable gate arrays (FPGAs), program specific integrated circuits (ASICs), program specific standard products (ASSPs), systems on a chip (SOCs), complex programmable logic devices (CPLDs), etc.

[0070] Additionally, any of the software-based embodiments (e.g., including computer-executable instructions for causing a computer to perform any of the disclosed methods) can be uploaded, downloaded, or remotely accessed via suitable communication means. Such suitable communication means include, for example, the Internet, the World Wide Web, an intranet, a software application, cable (including fiber optic cable), magnetic communication, electromagnetic communication (including radio frequency, microwave, and infrared communication), electronic communication, or other such communication means. In any of the above examples and embodiments, the provision of requests (e.g., data requests), instructions (e.g., data signals), commands (e.g., control signals), or any other communication between systems, components, devices, etc. can be by generation and transmission of appropriate electrical signals via wired or wireless connections.

[0071] Example of fabrication and experimental results Electrocatalyst-permeated porous layer as air-side electrode Symmetric cell solid oxide fuel cells (SOFCs) were fabricated using a uniaxial press to press GDC powder to a thickness of 1.5 mm. Button cell SOFCs were fabricated by stacking tape-cast anode support, anode functional material, and electrolyte material by hot roll lamination, followed by punching and sintering. Anode support layers (ASLs) were fabricated by mixing 60 wt% NiO and 40 wt% GDC with 3 wt% poly(methyl methacrylate) (PMMA), which was added to the slurry before mixing for porosity. Anode functional layers (AFLs) were fabricated by mixing 48 wt% NiO with 52 wt% GDC. Electrolyte dense tapes were fabricated using a similar method. A single high temperature (e.g., >1000 °C) treatment was used to sinter half-cells fabricated by roll processing, e.g., dense GDC supported on Ni-GDC.

[0072] Pr / Sm-lanthanide modified GDC scaffolds were then fabricated (e.g., via tape casting and blade coating) and sintered below 1000 °C. In particular, the scaffold ink was 11 , Sm2O3, and GDC powders were mixed at the respective weight percent of the precursor powders (e.g., 5Pr-GDC was prepared by mixing 5 wt.% Pr6O 11 -95% by weight of GDC). The mixed composition was then ball milled overnight in ethanol. The composition was then mixed with ESL441 ink vehicle (a Texanol-based composition sold by ElectroScience) and mixed with the mixture in a planetary centrifugal mixer until the ink vehicle to power ratio reached 1:1 (by weight) and all the ethanol was evaporated. For inks with PMMA, Chemisnow® MX-150 PMMA (sold by Soken Chemical & Engineering) was added in weight % to the mixture before ball milling. The inks were sintered in either symmetric or full cells at 950°C for 2 hours with an intermediate burn-out step (e.g., 400°C for 30 minutes) to burn out the PMMA and binder.

[0073] The electrocatalyst was then deposited within the scaffold and processed at <650 °C to obtain a complete battery. For example, a PSC multiphase electrocatalyst was synthesized by dissolving Pr-Sr-Co nitrates with metal cations in a (1-1-2) molar ratio. Pr 0.5 Sr 0.5 Chief of Staff 3-δ were the target phases. PrCoO3, Pr 0.5 Sm 0.5 Chief of Staff 3-δ , and Sr 0.5 Sm 0.5 Chief of Staff 3-δ Permeates of were prepared in a similar manner. The pH of the permeate mixture was balanced by adding ammonium hydroxide to the nitrate solution to a final pH of about 7. In addition, 3 wt% of a non-ionic surfactant (e.g., Triton X100 sold by Sigma Aldrich) was combined with NO3 and the combination was added as a surfactant to increase pore wettability. Note that the results shown in Figures 5A-5C were obtained using a solution that was not pH balanced and did not contain Triton X100. The cells were inoculated with 2 μL / 0.31 cm. 2 The scaffold was infiltrated with 0.1 μL of infiltrate per scaffold, followed by drying under reduced pressure for approximately 15 minutes to improve pore wettability. 2 The cells were then calcined at low temperature (e.g., 450°C for 30 min) to evaporate the nitrates, and the infiltration was repeated to achieve the desired loading. Note that one infiltration cycle corresponds to one low-temperature calcination in the furnace.

[0074] The results of symmetric cell tests of the PSC mixture on the GDC scaffold are shown in Figures 5A-5C. In situ high-temperature phase analysis of the infiltrated PSC particles revealed that PrO, which is stable up to at least 650 °C, 2-δ , Co3O4 and SrCoO 3-δWithout wishing to be bound by any particular theory, it is believed that the coexistence of these multiple phases associated with a highly nanostructured morphology contributes to the high electrochemical performance and low ASR. As shown in the Nyquist plot at 550 °C in Figure 5A, the scaffold calcination temperature of 950 °C for the GDC scaffold as the cathode resulted in a 0.25 Ω cm 2 sintering, which represents a 50-75% reduction over scaffolds sintered at higher temperatures. The scaffold sintering temperature effect is summarized in Figure 5B, which shows an inverse volcano behavior with the lowest ASR at 950 °C. Below 950 °C, low sintering resulted in a higher ASR, and above 950 °C, scaffold densification could reduce the triple-phase boundary length. However, other scaffold configurations could achieve minimal ASR at sintering temperatures other than 950 °C. Figure 5C shows the distribution of relaxation time (DRT) analysis, with the major peaks labeled P1-P3. P1 and P2 (τ ≈ 10 -3 s) is typically due to interfacial charge transfer and increases slightly. In contrast, P3, which is due to surface exchange reactions, exhibits a 98% reduction in energy loss compared to the conventional SSC-GDC cathode.

[0075] While the examples in Figures 5A-5C are for a simple GDC scaffold, Figures 6A-6D demonstrate the effect of further lanthanide addition (e.g., Pr and / or Sm) to the scaffold. Different ceria-based scaffolds with different PSC loadings (e.g., number of infiltration cycles) were incorporated into full cells. The current-voltage (iV) and EIS at 550 °C of these full cells are shown in Figures 6A-6B, respectively. For the pure GDC scaffold, the polarization resistance is only 0.25 Ω cm 2 However, the low electronic conductivity of the cathode was 1.25 Ω cm 2 This resulted in a high resistivity of 0.2 Ω cm at 550 °C, thereby limiting the peak power density (PPD) to only 175 mW / cm. A 20 μm dense GDC electrolyte typically has a resistivity of 0.2 Ω cm at 550 °C. 2 , so the apparent ohmic loss from the scaffold is effectively around ∼1 Ω cm.

[0076] However, as shown in Figure 6C, by modifying the GDC scaffold with the addition of Pr and / or Sm, the ohmic losses can be dramatically reduced and the PPD of the whole cell can be improved. Notably, with increasing Pr / Sm loading, the ohmic ASR of the whole cell (with 20 μm GDC electrolyte) decreases, suggesting that the electronic conductivity of the scaffold increases. 11 When added to the scaffold (0.5Pr-GDC), the ohmic ASR was 1.25 Ω cm 2 to 1.1 Ω cm 2 The concentration of PrO was 5% by weight. 11 Adding (5Pr-GDC) increases the ohmic ASR by an additional 0.5Ωcm 2 Comparing the 3-cycle flooded PSC cells, the 5 wt.% PrO 11 With the addition of 5 wt% Sm2O3 to (5Pr-5Sm-90GDC), the ohmic ASR was 0.3 to 0.24 Ω cm at 550°C. 2 Although the 5Pr-GDC cell has a slightly higher peak power density compared to the 5Pr-5Sm-90GDC cell in this control experiment, the 5Pr-5Sm-90GDC contributed the lowest ohmic losses to the cell performance. These results suggest that the addition of lanthanides to the GDC scaffold improves the electrical conductivity, leading to a lower ohmic ASR and higher performance.

[0077] The effect of electrocatalyst loading is summarized in Figure 6D, where one cycle is approximately 1-2 mg of infiltrated oxide. As the PSC loading increases, the electrode ASR decreases due to the increase in the number of active sites. Furthermore, with increasing infiltration loading (1 cycle vs. 3 cycles), the ohmic ASR decreases from 0.5 Ω cm 2 to 0.25 Ω cm 2 Without wishing to be bound by any particular theory, the decrease in ohmic ASR in response to increased loading may be due to (1) increased connectivity of the conductive electrocatalyst and / or (2) doping of the scaffold with permeants during synthesis and / or testing. The decrease in ohmic ASR was 0.22 W / cm for one permeation cycle loading. 2from 0.5 W / cm at 550 °C with three infiltration cycles. 2 Above three infiltration cycles, the PSCs can begin to aggregate.

[0078] The PSC-infiltrated 5Pr-5Sm-90GDC scaffold can be further improved by tailoring the electrode microstructure, as shown in Figures 10A-10F, and the high performance results of the optimized battery are shown in Figures 7A-7F. In particular, the porosity of the scaffold can increase the surface area to allow higher electrocatalyst loading and overcome the mass transport limitations. As a result, the 20 μm electrolyte battery can achieve 0.85 W / cm at 550 °C, as shown in Figure 7A. 2 The 10 μm electrolyte cell exhibited a PPD of 1 W / cm at 550 °C. 2 , 0.6 W / cm at 500°C 2 Figure 7B shows that the polarization impedance is only ~0.07 Ω cm 2 The ohmic part shows that both cells, e.g., 0.15 Ω cm for the 20 μm and 10 μm configurations, respectively. 2 and 0.09 Ω cm 2 was considered to be the major loss.

[0079] The microstructure of an aged 20 μm electrolyte cell can be seen in Figure 7C. As suggested by Figure 7D, the PSC electrocatalysts exhibit high activity and durability, and their nanoscale state is preserved after 500 h at 550 °C. This may be due to the infiltration calcination temperature. Specifically, PSC nanoparticles only have a thermal resistance of 650 °C or less. Previous attempts at infiltration have utilized much higher temperatures (e.g., above 800 °C). For example, Pr on LSCF-SDC scaffolds synthesized at high temperatures of 800–1300 °C 0.4 Sr 0.6 Chief of Staff 3-δ is 0.15 Ω cm at 750°C 2 In contrast, the multiphase PrO x , CoO x and SrCoO 3-δ is 0.25 Ω cm at 550°C 2Achieve low ASR with high durability. - The aging results for the 20 μm electrolyte cell in Figures 7E-7F show that the majority of the PPD degradation occurs in the first 50 hours. Without wishing to be bound by any particular theory, it is believed that the PPD degradation is due to a slight coarsening of the PSC nanoparticles. As shown in Figures 7C-7D, the size of the PSC particles initially grew from ~20 nm to ~100-200 nm after 500 hours. This is further supported by Figure 7E, which shows a total electrode ASR of 0.07 Ω cm 2 (t=0 hours) to 0.11Ωcm 2 (t=50 h) and then stabilized for the duration of the test (t=500 h). The ohmic ASR showed a similar trend, which may be attributed to the loss of electronic connectivity due to particle agglomeration. Note that one primary electronic conduction path is through the PSC-infiltrated particles connected on the surface. Nevertheless, the long-term galvanostatic test showed a constant current of 200 mA / cm over the 500-h long-term test, especially after the first 50 h. 2 shows very little degradation at

[0080] To understand the full potential of the proposed electrode design, the whole cell was tested with the cathode exposed to pure oxygen (pO2 = 1 atm) to simulate pressurized operation, and the results are shown in Figures 8A-8D. The highly active nanocatalyst dispersed on the MIEC scaffold, in combination with the highly conductive GDC electrolyte, results in very high performance for fuel cells. The EIS sweep in Figure 8A shows that the whole cell exhibited a resistance of only 0.031 Ω cm at 650 °C. 2 The results show that the cell has a total impedance of 4.01 W / cm at 650 °C. Most of the energy loss (e.g., 91.3%) can be attributed to ohmic resistance, which means that the oxygen reduction reaction (ORR) overpotential does not limit the cell's performance. Furthermore, the non-ohmic impedance results in a significantly lower ASR than the ohmic impedance above 500 °C, as shown in Figure 8B. The system performance can be further improved by reducing the electrolyte thickness. Nevertheless, the extremely low total ASR means that the cell has a total ASR of 4.01 W / cm at 650 °C, as shown in Figure 8C.2 , 1.87 W / cm at 550°C 2 , and 0.48 W / cm at 450°C. 2 Furthermore, the constant potential (0.75 V) aging in Figure 8D shows a PPD of ∼0.86 W / cm after 100 h. 2 The MOSFETs exhibit a constant open circuit voltage (OCV) as well as regulation to a constant power.

[0081] The above examples use Pr-Sr-Co infiltrates for the cathode, but the presence of Sr and Co may suffer from stability and supply chain issues, respectively. However, other materials can be used as electrocatalyst infiltrates to similar effect. For example, Sr was replaced with other large radius 2 / 3+ elements (Figures 9A-9B) and Co was replaced with other small transition metals (Figures 9C-9D). Compared to the state-of-the-art LSCF-GDC cathode, Figures 9A-9B show that all 13 compositions exhibit ~5x lower ASR, with most offering at least 10x improvement over the entire temperature range. Thus, regardless of composition, the nanostructuring produced from this novel low-temperature cathode preparation approach can achieve such low ASR.

[0082] The cathodic stability of Sr-substituted infiltrates was evaluated by probing the ASR of symmetric cells at 600 °C for ~200 h. As shown in Figure 9C, the ASR of all compositions increased over time, but the suppression of the decomposition rate of Pr-La-Co resulted in an ASR nearly identical to PSCs after ~50 h of aging. The cathodic stability of Co-substituted infiltrates was also evaluated by probing the ASR of symmetric cells at 600 °C for ~200 h. As shown in Figure 9D, infiltrates containing Cu, Fe, Ni, and Zn showed negligible or negative degradation over 200 h. Further analysis shows that this trend continued beyond 1800 h. Compared to Co, the three alternatives (Fe, Ni, or Zn) offered competitively lower ASR, were more abundant, and were of less geopolitical concern.

[0083] Air side porous functional layer Doped ceria electrolytes are state-of-the-art low-temperature solid oxide electrolytes due to their high ionic conductivity and good material compatibility. 4+ / 3+ Due to the different degrees of redox state (due to the electrochemical potential gradient), the total electronic conductivity in the electrolyte is directly affected by the thickness, the gas environment on either side, and the temperature. Since the reduction of cerium is restricted to the region near the anode, a thicker doped ceria layer has a higher ion migration number t O2- However, the increased thickness also contributes to higher ohmic losses, hindering performance at low temperatures. t Measured OCV for t O2- (t O2- =OCV / V t ), a typical 20 μm thick GDC electrolyte will have a V of 80% at 500 °C. t (theoretical potential) only.

[0084] t for thin GDC electrolytes (e.g., 20 μm or less) at low temperatures (e.g., ≦650°C) O2- To increase the O2 concentration, a porous functional layer (PFL) was provided on the air side of the electrolyte, increasing the exposure of this ceria layer to oxygen partial pressure (pO2). In addition, the intrinsic electronic charge carrier density in the PFL is significantly low due to the gas-solid equilibrium of the PFL in air. Furthermore, by engineering the PFL with active dopants (e.g., Pr), oxygen transport in the PFL can be promoted, resulting in a synergistic effect that significantly improves cell performance. As a result, SOCs incorporating such structures can exhibit much higher OCV, lower area specific resistance (ASR), higher performance, and increased durability, for example, achieving cell operation for more than 2000 hours without performance loss.

[0085] Solid oxide fuel cell (SOFC) button cells were fabricated using tape casting. The anode support layer (ASL) was fabricated using tape casting method. In particular, 60 wt% NiO and 40 wt% GDC were combined, followed by adding 3 wt% PMMA to the slurry to achieve the desired porosity. The anode functional layer (AFL) was also fabricated by tape casting using 48 wt% NiO and 52 wt% GDC. GDC electrolytes with thicknesses of 20 μm, 15 μm, and 10 μm were fabricated by tape casting. The ASL (thickness ∼500 μm), AFL (thickness ∼15 μm), and electrolyte (thickness 20 μm, 15 μm, or 10 μm) were then laminated together using a roll laminator, followed by sintering at 1450 °C for 4 h to form a half cell. The SSC-GDC cathode ink was prepared using SSC, GDC, and the ESL441 ink vehicle (a Texanol-based composition sold by ElectroScience). The PFL layer was prepared in the same manner as the cathode ink, but with the addition of PrO 11 The PFL or SSC-GDC cathode ink was then applied to a 0.31 cm2 31 cm2 32 ... 2 The active area cathode was deposited on a Ni-GDC / GDC half-cell, and then the cathode and PFL were co-fired at 950 °C for 2 h.

[0086] Electrolyte-supported cells were used for ion transfer number measurement studies, where tape-cast GDC supports (200–300 μm) were sintered at 1450 °C for 4 h. Ni-GDC (48% NiO-52% GDC) ink, prepared in a similar manner as the cathode ink, was applied to the cell and sintered at 1200 °C for 2 h. SSC-GDC / PFL was applied to the other side of the electrolyte and sintered at 950 °C for 2 h. To make symmetric cells, GDC powder was pressed to make pellets approximately 1.5 mm thick. SSC-GDC composite cathode paste and PFL (depending on geometry) were applied to both sides of the symmetric cell and sintered at 950 °C for 2 h. For infiltration of the SSC-GDC composite cathode, praseodymium nitrate was first dissolved in deionized water to make a 1 M praseodymium nitrate solution, and then 6 μL of the 1 M praseodymium nitrate solution was used to infiltrate the cathode. The infiltrated cathode was then placed under vacuum for 10 min. The cell was placed under vacuum and then calcined in a furnace at 450°C for 30 minutes to dry the nitrate precursor.

[0087] Sr 0.5 Sm 0.5 Chief of Staff 3-δ -Ce 0.9 Gd 0.1 O 2-δWe fabricated SOFCs with the layer configuration of FIG. 2B, with a composite cathode (SSC-GDC) of Ni-GDC and an intercalated PFL (e.g., SSC-GDC / PFL / GDC / Ni-GDC). As shown in FIG. 11A, the fabricated structure shows separate layers for the cathode, PFL, dense electrolyte layer (DEL), and anode. The porous microstructure of the PFL is also reflected in the SEM inset of FIG. 2B. Two cells were tested with the same total GDC thickness; one was composed of 10 μm DEL + 10 μm PFL and the other was composed of 20 μm DEL. The results in FIG. 11B highlight the impact of the porous engineered microstructure. In particular, the PFL provides two performance enhancements to the cell: (1) increased open circuit voltage (OCV), and (2) decreased impedance. For example, by adding the PFL layer, the OCV increased from 0.91 V to 0.98 V at 500 °C and from 0.88 V to 0.95 V at 550 °C, an 8% improvement compared to the DEL-only configuration. Furthermore, as shown in the EIS of Figures 11C-11D, by replacing the 10 μm DEL with a PFL, the ohmic ASR increased to 0.25 Ω cm at 550 °C. 2 to 0.17Ωcm 2 and 0.46 Ω cm at 500°C 2 to 0.34 Ω cm 2 It drops to.

[0088] In both of the fabricated examples, the total GDC thickness is the same (e.g., 20 μm). However, when using a PFL between the DEL and the cathode, half of the thickness is porous. This is expected to increase the ohmic ASR due to the constriction of ion transport in the porous structure. However, the provision of a PFL leads to a decrease in the ASR. Furthermore, the PFL (0.14 Ω cm at 550 °C) 2 and 0.47 Ω cm at 500°C 2 ) non-ohmic polarization due to DEL alone (0.55 Ω cm at 550 °C) 2 and 1.37 Ω cm at 500°C 2 The addition of PFL significantly increases the maximum power density (PPD) (as much as 257% at 550 °C) and reduces it to 0.36 W / cm at 500 °C. 2 , which rises to 0.76 W / cm at 550°C.

[0089] As shown in Figures 12A-12D, SOFCs with different DEL thicknesses and PFL concentrations (e.g., 0, 0.5, and 5.0 wt% Pr) were tested to understand the OCV enhancement mechanism of the PFL. The reference PFL concentration referenced throughout the figures is (0.5 wt% PrO 11 The PFL is the PFL with different Pr concentrations on the 200 μm GDC substrate, and all other wt% configurations are denoted as (X wt% Pr+GDC). The effect of PFL on OCV enhancement was tested by depositing 10 μm PFL with different Pr concentrations on the 200 μm GDC substrate. As shown in FIG. 12A, the reduction in OCV at low GDC thickness can be minimized or at least reduced by using PFL. Due to the MIEC in GDC, the apparent ion migration number t of 200 μm GDC O2- reaches only 0.91 at 500 °C. As the temperature increases, both the oxygen nonstoichiometry, x, and electronic defects are thermally activated, and t O2- is further reduced to 0.85 at 650 °C. For the PFL, t O2- is significantly improved, and this enhancement is more effective at low temperatures.

[0090] FIG. 12B shows the effect of PFL on OCV for a thin anode-supported 20 μm GDC electrolyte with PFL thickness ranging from 10 μm to 20 μm. The GDC baselines for 200 μm and 20 μm DEL thicknesses are also shown in FIG. 12B as open symbols with solid lines. Not only the theoretical voltage, but also the t O2-The levels of . As the GDC thickness is reduced from 200 μm to 20 μm, the OCV drops by more than 10% due to the higher electrochemical gradient (air / H2@3%H2O) across the thin electrolyte (5.8 vs. 58 mV / μm for 200 to 20 μm thick GDC, respectively), forcing a reduction in the Ce4+ / 3+ redox couple and increasing electronic conductivity. Compared to the 20 μm GDC baseline, the presence of PFL increases the OCV at all temperatures. With an increase in the DEL thickness to 200 μm, the OCV reaches 93% and 90% of the theoretical value at 500 and 550 °C, respectively. However, the addition of 15 μm or 20 μm PFL to a 20 μm thick GDC DEL can increase its OCV to match that of a 200 μm thick GDC DEL. In fact, such a PFL-DEL combination exceeded the 200 μm thick GDC DEL as the temperature decreased below 600° C. This external structure design enhances the OCV more effectively than simply increasing the GDC thickness, since the OCV of the 20 μm thick DEL+15 μm thick PFL (total thickness 35 μm) is higher than that of the 200 μm thick GDC with significantly lower ASR.

[0091] Since the extrinsic structural design can minimize electronic conduction in the GDC, the thickness of the DEL can be minimized, or at least reduced, to reduce ohmic losses for oxygen transport without sacrificing the OCV. Figure 12C shows the results of the 10 μm PFL (0.5 wt. % PrO) with various thicknesses. 2-x The effect of the thickness of the electrolyte (GDC) on the ohmic ASR was linearly dependent on the varying electrolyte thickness, with the lowest value achieved for the 10 μm DEL sample. Furthermore, the ohmic ASR was ~0.3 Ω cm at 500 °C. 2 The ohmic ASR of 15 μm DEL + 10 μm PFL could exceed 1 V. The OCV of the 15 μm DEL + 10 μm PFL configuration maintained a high OCV (comparable to that of the 20 μm DEL + 10 μm PFL configuration) but did not suffer from ohmic losses in the 20 μm thick electrolyte. This suggests that DELs greater than 15 μm have minimal effect on increasing the OCV but contribute to ohmic losses.

[0092] FIG. 12D shows the effect of Pr doping level in the PFL on the OCV enhancement for 10 μm DEL + 10 μm PFL. Adding Pr as a homogeneous dopant in the PFL reduces the OCV enhancement somewhat. Without wishing to be bound by any particular theory, it is believed that the external porous structure of the PFL is the main cause of the reduced electronic conduction in the GDC layer. Nevertheless, the addition of Pr can have a significant benefit on the electrochemical performance. The effect of PFL on the electrochemical performance enhancement was determined using a symmetric cell configuration. FIG. 13A shows the Nyquist plot of the SSC-GDC cathode with and without the presence of PFL. The addition of PFL reduces the polarization impedance, suggesting that the Pr concentration in the PFL can play a role in the overall cathode performance. The pure porous GDC layer reduced the cathode ASR due to the increased active area at the cathode three-phase boundary, and the addition of multivalent Pr further improved the electrochemical performance. For example, 0.5 wt% PrO 2-x With PFL, 3.2 Ω cm without PFL 2 had the lowest cathodic ASR of 0.7 Ω cm compared to 0.18 wt. However, the higher doping level of Pr (5 wt.%) may act as a sintering aid since the microstructure appears to have a densified composition resulting in a reduction in the active surface area.

[0093] A PFL / GDC symmetric cell (without SSC-GDC cathode) was further tested to determine the electrochemical activity of the PFL separately. The Arrhenius plots of the cathode ASR in Figure 13B-C show that the PFL lacks sufficient cathodic activity by itself, regardless of the Pr doping level, since the electrode polarization is 2-3 orders of magnitude higher than the cathode above the PFL configuration. The influence of Pr is further shown in Figure 13B, since the PFL operating without a cathode had an ASR that was orders of magnitude higher than the conventional SSC-GDC cathode (as shown in Figure 13C), confirming that the PFL does not have sufficient cathodic activity by itself. There is further evidence that the PFL does not have sufficient electrochemical activity to function as a cathode. In particular, Pr plays a role in increasing the cathodic activity in the PFL. Thus, the PFL shows a ∼10% increase in ASR at 500 °C compared to that without Pr.4 Ωcm 2 From the order of magnitude, in the PFL, the Pr-free and SSC-GDC cathodes were 10 2 Ωcm 2 This suggests that Pr enhances the electrochemical activity during PFL.

[0094] The distribution of relaxation times (DRT) analysis in FIG. 13D further reveals how the PFL improved the cathode performance. SSC-GDC (without PFL) (curve Y) typically has a time constant (τ) of 10 -3 ~10 0 (sec). With the addition of PFL, this peak intensity decreased, suggesting that PFL promotes the surface reaction step. Based on the results of further aging at 500°C and 600°C in Figure S7 of U.S. Provisional Application No. 63 / 265,921 below, which is incorporated herein by reference, SSC-GDC with PFL was stable alone for over 1200 hours at 500°C and 600°C, respectively, with a resistivity of ∼0.8 Ω cm. 2 and 0.25 Ω cm 2 It can be seen that the electrode ASR of 100 μm was maintained. The aging results at 600 °C suggested that the stability of SSC-GDC+PFL was significantly enhanced compared to the baseline SSC-GDC.

[0095] To help illustrate the effect of PFL on cathode performance, an isothermal oxygen partial pressure (pO2) dependence study and corresponding DRT analysis were performed, the results of which are shown in Figures 13E-13F. The double log plot of cathode ASR versus log(pO2) in Figure 13E shows that by adding PFL, the impedance drops at all pO2s, with a slope change from 1 / 4 to 1 / 6 indicating a change in the rate-limiting step in the surface reaction. The DRT results in Figure 13F show that deconvoluting the impedance results shows that PFL reduced the reaction losses in the surface reaction zone (τ = 10 -3 -10 0 (s)).

[0096] Surface modification (SM) was performed on the PFL-based cells to further improve their durability and performance. In particular, surface modification is described in Huang et al., “Nanointegrated, High-Performing Cobalt-Free Bismuth-Based Composite Cathode for Low-Temperature Solid Oxide Fuel Cells.” ACS Appl. Mater.Interfaces, 2018, 10(34): pp.28635-43. The results are shown in Figures 14A-14D. As shown in Figure 14A, the PFL-based SSC-GDC SOFC achieved 0.35 W / cm at 500 °C in H2. 2 The Pr surface-modified cathode (Pr-SM SSC-GDC) had a PPD of 0.55 W / cm 2 As shown in Figure 14B, the Pr-SM SSC-GDC / PFL cell achieved a PPD of 0.3 Ω cm at 500 °C. 2 and SSC-GDC / PFL has a total ASR of 0.75 Ω cm at 500°C. 2 Thus, the cathode surface modification significantly reduced the battery ASR.

[0097] 0.2A / cm 2 The cells were aged at 500 °C and 550 °C with humidified H at 40 °C, and the terminal voltage and corresponding cell ASR are shown in Figures 14C-14D, respectively. As shown in Figure 14C, the SSC-GDC / PFL cell (NN curve) exhibited high durability for over 800 h at 550 °C, demonstrating that the porous design of the PFL can maintain its functionality even after long-term aging. However, the Pr-SM cell (OO curve) further enhanced the performance, allowing it to have the same power density while operating at 50 °C. The Pr-SM cell achieved a maximum power density of 0.5 W / cm at 500 °C. 2 The PPD of 1.05% was 0.01, indicating excellent stability for over 2000 hours of operation. The cell ASR of Pr-SM SSC-GDC / GDC / Ni-GDC is shown in Figure 14D, resolving ohmic and non-ohmic contributions. No significant degradation was observed during 2000 hours of operation.

[0098] Further examples of the disclosed technology In view of the above implementations of the disclosed subject matter, the present application discloses additional examples in the appendices listed below. It should be noted that any feature of the appendices alone, or two or more features of the appendices taken in combination, and optionally combined with one or more features of one or more additional appendices, are also included within the scope of the disclosure of the present application.

[0099] Appendix 1. a non-porous oxide layer configured to conduct oxygen ions and act as a solid electrolyte; one or more first porous layers disposed on a first side of the non-porous oxide layer; one or more second porous layers disposed on a second side of the non-porous oxide layer opposite the first side; the non-porous oxide layer has a density greater than each of the first and second porous layers; the electronic conductivity of the non-porous oxide layer is less than 25% of the ionic conductivity of the non-porous oxide layer; for each of the first and second porous layers, the electronic conductivity of the respective porous layer is greater than 25% of the ionic conductivity of the respective porous layer; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to operate as a second electrode.

[0100] Appendix 2. a non-porous oxide layer configured to conduct oxygen ions and act as a solid electrolyte; a porous functional layer disposed on the first surface of the non-porous oxide layer; one or more first porous layers disposed on a side of the porous functional layer opposite the non-porous oxide layer; one or more second porous layers disposed on a second side of the non-porous oxide layer opposite the first side; the non-porous oxide layer has a density greater than the density of the porous functional layer; the electronic conductivity of the non-porous oxide layer is less than 25% of the ionic conductivity of the non-porous oxide layer; the porous functional layer is effective to increase the ion mobility number of the non-porous oxide layer and the porous functional layer to at least 0.9 at a temperature of 550° C. or less; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to operate as a second electrode.

[0101] Appendix 3. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of appendices 1 and 2, A solid oxide battery, wherein the one or more second porous layers comprise a nickel cermet of ceria, a nickel cermet of zirconia, or a mixed ionic electronic conducting oxide.

[0102] Appendix 4. The solid oxide battery according to any one of the sections or examples of this specification, particularly the solid oxide battery according to any one of appendices 1 to 3, 11. A solid oxide battery, wherein the one or more second porous layers are formed from a ceria nickel cermet, a zirconia nickel cermet, a gallate nickel cermet, a molybdate, a molybdate nickel cermet, a chromate, a chromate nickel cermet, a vanadate, or a vanadate nickel cermet.

[0103] Appendix 5. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 4, A solid oxide battery, wherein the one or more first porous layers comprise ceria or bismuth oxide.

[0104] Appendix 6. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 5, A solid oxide battery, wherein the one or more first porous layers comprise doped ceria, cubic bismuth oxide, rhombohedral bismuth oxide, or doped rhombohedral bismuth oxide.

[0105] Appendix 7. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 6, A solid oxide battery, wherein the one or more first porous layers comprise doped ceria doped with one or more lanthanides.

[0106] Appendix 8. A solid oxide battery according to any of the sections or examples of the present specification, particularly according to Appendix 7, A solid oxide battery in which the one or more lanthanides added are praseodymium, samarium, or both praseodymium and samarium.

[0107] Appendix 9. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of appendices 1 to 8, A solid oxide cell, wherein the one or more first porous layers are infiltrated with one or more electrocatalyst oxides.

[0108] Appendix 10. A solid oxide battery according to any of the sections or examples of the present specification, particularly according to Appendix 9, 1. A solid oxide cell, wherein the one or more electrocatalyst oxides comprise one or more multi-phase electrocatalysts formed by at least A and B, and the molar ratio of A:B in the one or more multi-phase electrocatalysts is about 1:1.

[0109] Appendix 11. A solid oxide battery as described in any of the sections or examples of the present specification, particularly as described in Appendix 10, comprising: A solid oxide battery, wherein A is a Group 2 element, Group 3 element, or a lanthanide, and B is a Period 4 element.

[0110] Appendix 12. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 10 to 11, A is selected from the group consisting of praseodymium (Pr), calcium (Ca), strontium (Sr), yttrium (Y), lanthanum (La), neodymium (Nd), samarium (Sm), dysprosium (Dy), and erbium (Er); B is selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and zinc (Zn).

[0111] Appendix 13. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 4, 1. A solid oxide battery, wherein the one or more first porous layers comprise ceria or bismuth oxide, or a composite material formed from (i) ceria or bismuth oxide and (ii) one or more electronically conductive and electrocatalytic oxides.

[0112] Appendix 14. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 4, comprising: The one or more first porous layers may be made of lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt ferrite (LSCF), yttria stabilized zirconia (YSZ), scandia stabilized zirconia (SSZ), gadolinia doped ceria (GDC), samaria doped ceria (SDC), samaria neodymium doped ceria (SNDC), erbia stabilized bismuth oxide (ESB), dysprosium tungsten stabilized bismuth oxide (DWSB), yttria stabilized bismuth oxide (YSB), rhombohedral bismuth oxide, strontium and magnesium doped lanthanum gallate (LSGM), strontium samarium cobalt oxide (SSC), and nickel oxide Ln2NiO. 4+δ (Ln is a lanthanide).

[0113] Appendix 15. A solid oxide battery as described in any of the sections or examples herein, particularly in Appendix 1, comprising: The solid oxide battery further comprising a porous functional layer disposed between and in direct contact with one of the first porous layer and the non-porous oxide layer.

[0114] Appendix 16. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 2 to 15, A solid oxide battery, wherein the porous functional layer consists essentially of ceria or bismuth oxide.

[0115] Appendix 17. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 2 to 16, A solid oxide battery, wherein the porous functional layer is configured to increase the open circuit voltage of the solid oxide battery.

[0116] Appendix 18. A solid oxide battery as described in any of the sections or examples of the present specification, particularly as described in Appendix 17, comprising: The open circuit voltage is at least 0.9 V at a temperature in the range of 500 to 550° C. (inclusive).

[0117] Appendix 19. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 2 to 18, the thickness of the porous functional layer along the first direction from the first electrode to the second electrode is about 20 μm or less; and / or A solid oxide battery, wherein the thickness of the non-porous oxide layer along the first direction is about 20 μm or less.

[0118] Appendix 20. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 19, At least one of the one or more second porous layers is configured to operate as an anode and at least one of the one or more first porous layers is configured to operate as a cathode when electrochemical oxidation occurs on the second side; and / or At least one of the one or more second porous layers is configured to operate as a cathode and at least one of the one or more first porous layers is configured to operate as an anode when reduction occurs on the second side.

[0119] Appendix 21. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 20, comprising: the one or more first porous layers are configured to receive an input stream having an oxygen concentration in the range of 20 to 100% (mole fraction), inclusive; The one or more second porous layers are configured to receive a fuel, and the solid oxide cell is configured to operate as a solid oxide fuel cell (SOFC) by electrochemically oxidizing the fuel to produce electricity, a solid oxide cell.

[0120] Appendix 22. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 20, comprising: the one or more second porous layers are configured to receive an input stream comprising HO and / or CO; A solid oxide cell configured to operate as a solid oxide electrolysis cell (SOEC) by electrochemically reducing H2O or CO2 on a second side and generating O2 on a first side.

[0121] Appendix 23. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 22, comprising: the solid oxide cell is configured to reverse polarity to switch between operation as a solid oxide fuel cell (SOFC) and operation as a solid oxide electrolysis cell (SOEC); the solid oxide cell is configured, during a first mode of operation, to electrolyze HO and / or CO provided to one of the first and second electrodes to produce a fuel; The solid oxide cell is configured to oxidize a fuel to produce electricity during a second mode of operation.

[0122] Appendix 24. A solid oxide battery according to any one of the sections or examples of the present specification, particularly any one of Appendices 1 to 23, comprising: A solid oxide battery, wherein the non-porous oxide layer comprises ceria, zirconia, bismuth oxide, or lanthanum gallate.

[0123] Appendix 25. 1. A method for manufacturing a solid oxide battery, comprising: (a) providing one or more first precursors for forming one or more second porous layers; (b) providing one or more second precursors for forming a non-porous oxide layer on the one or more first precursors; (c) sintering the first and second precursors at a temperature equal to or greater than the first threshold to form one or more second porous layers on a second side of the non-porous oxide layer; (d) providing one or more third precursors for forming one or more first porous layers on a first side of the non-porous oxide layer opposite the second side; (e) sintering the one or more third precursors at a temperature below a first threshold to form one or more first porous layers on the first side of the non-porous oxide layer; the non-porous oxide layer has a density greater than the densities of the first and second porous layers; for each of the first and second porous layers, the electronic conductivity of the respective porous layer is greater than 25% of the ionic conductivity of the respective porous layer; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to act as a second electrode.

[0124] Appendix 26. 1. A method for manufacturing a solid oxide battery, comprising: (a) providing one or more first precursors for forming one or more second porous layers; (b) providing one or more second precursors for forming a non-porous oxide layer on the one or more first precursors; (c) sintering the first and second precursors at a temperature equal to or greater than the first threshold to form one or more second porous layers on a second side of the non-porous oxide layer; (d) providing one or more third precursors for forming a porous functional layer on a first side of the non-porous oxide layer opposite the second side; (e) providing one or more fourth precursors for forming one or more first porous layers on the one or more third precursors; (f) sintering the third and fourth precursors at a temperature below a first threshold to form a non-porous oxide layer on a first side of the non-porous oxide layer and to form the first porous layer on a side of the non-porous oxide layer opposite the first porous layer; the non-porous oxide layer has a density greater than the densities of the first porous layer and the second porous layer; the non-porous oxide layer has, for each of the first and second porous layers, an electronic conductivity of each porous layer that is greater than 25% of an ionic conductivity of each porous layer; The porous layer has an effect of increasing the ion migration number of the non-porous oxide layer and the porous functional layer to at least 0.9 at a temperature of 550° C. or less; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to act as a second electrode.

[0125] Appendix 27. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 26, comprising: The method wherein the first threshold is about 1000°C.

[0126] Appendix 28. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 27, comprising: sintering the one or more third precursors or the third and fourth precursors is carried out at a temperature of about 950° C.; Sintering of the first and second precursors is carried out at a temperature of about 1450° C.; or A method that is carried out in both of the above ways.

[0127] Appendix 29. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 28, comprising: The method, wherein the one or more second porous layers comprise a nickel cermet of ceria, a nickel cermet of zirconia, or a mixed ionic electronic conducting oxide.

[0128] Appendix 30. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 29, comprising: The method, wherein the one or more second porous layers are formed from a nickel cermet of ceria, a nickel cermet of zirconia, a nickel cermet of gallate, a molybdate, a nickel cermet of molybdate, a chromate, a nickel cermet of chromate, a vanadate, or a nickel cermet of vanadate.

[0129] Appendix 31. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 30, comprising: The method, wherein the one or more first porous layers comprise ceria or bismuth oxide.

[0130] Appendix 32. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 31, comprising: The method, wherein the one or more first porous layers comprise doped ceria, cubic bismuth oxide, rhombohedral bismuth oxide, or doped rhombohedral bismuth oxide.

[0131] Appendix 33. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 32, comprising: The method, wherein the one or more first porous layers comprise doped ceria doped with one or more lanthanides.

[0132] Appendix 34. The method according to any of the sections or examples herein, particularly appendix 33, comprising: A process wherein the one or more lanthanides added are praseodymium, samarium, or both praseodymium and samarium.

[0133] Appendix 35. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 34, comprising: The method further comprising, after forming the one or more first porous layers, infiltrating at least one of the one or more first porous layers with one or more electrocatalyst oxides.

[0134] Appendix 36. The method according to any of the clauses or examples herein, in particular the method according to appendix 35, wherein the penetration comprises: (f1) providing a dose of one or more electrocatalysts in solution to at least one of the one or more first porous layers; (f2) exposing at least one of the one or more first porous layers having the dose to a vacuum; (f3) repeating (f1) and (f2) with another dosage of one or more electrocatalysts in the solution; and (f4) after (f3), exposing the one or more first porous layers to a temperature of about 450° C. to evaporate or combust the solution.

[0135] Appendix 37. The method according to any one of the sections or examples of this specification, particularly any one of appendices 35 to 36, comprising: The method, wherein the one or more electrocatalyst oxides comprise a multi-phase electrocatalyst formed by at least A and B, and the molar ratio of A:B in the one or more multi-phase electrocatalysts is about 1:1.

[0136] Appendix 38. The method according to any of the sections or examples herein, particularly appendix 37, comprising: The method wherein A is a Group 2 element, Group 3 element, or a lanthanide and B is a Period 4 element.

[0137] Appendix 39. The method according to any one of the sections or examples of this specification, particularly any one of appendices 37 to 38, comprising: A is selected from the group consisting of praseodymium (Pr), calcium (Ca), strontium (Sr), yttrium (Y), lanthanum (La), neodymium (Nd), samarium (Sm), dysprosium (Dy), and erbium (Er); and / or The method wherein B is selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and zinc (Zn).

[0138] Appendix 40. The method according to any of the clauses or examples herein, in particular any one of appendices 25 to 39, wherein providing one or more third precursors of (d) comprises: (d1) incorporating ceria with or without one or more lanthanide oxides into the ink; (d2) mixing a pore-forming agent into the ink;

[0139] Appendix 41. The method of any of the sections or examples herein, in particular the method of appendix 40, comprising: The method wherein the pore-forming agent comprises poly(methyl methacrylate).

[0140] Appendix 42. The method according to any section or example herein, particularly any one of Appendixes 25 to 30, wherein the one or more first porous layers comprise ceria, bismuth oxide, or a composite material formed from (i) ceria or bismuth oxide and (ii) one or more electronically conductive and electrocatalytic oxides.

[0141] Appendix 43. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 30, The one or more first porous layers may be selected from the group consisting of lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt ferrite (LSCF), yttria stabilized zirconia (YSZ), scandia stabilized zirconia (SSZ), gadolinia doped ceria (GDC), samaria doped ceria (SDC), samaria neodymium doped ceria (SNDC), erbia stabilized bismuth oxide (ESB), dysprosium stabilized bismuth oxide (DWSB), yttria stabilized bismuth oxide (YSB), rhombohedral bismuth oxide, strontium and magnesium doped lanthanum gallate (LSGM), strontium samarium cobalt oxide (SSC), and nickel oxide LnNiO. 4+δ (Ln is a lanthanide).

[0142] Appendix 44. The method according to any of the clauses or examples herein, particularly appendix 25, comprising: Prior to (d), providing one or more fourth precursors for forming a porous functional layer on the first side of the non-porous oxide layer; Providing (d) includes providing one or more third precursors over the one or more fourth precursors; The method of (e), wherein the sintering forms the one or more fourth precursors as a porous functional layer disposed between and in direct contact with one of the first porous layer and the non-porous oxide layer.

[0143] Appendix 45. The method according to any one of the sections or examples of this specification, particularly any one of appendices 26 to 44, comprising: The method, wherein the porous functional layer consists essentially of ceria or bismuth oxide.

[0144] Appendix 46. The method according to any one of the sections or examples of this specification, particularly any one of appendices 26 to 45, comprising: The method, wherein the porous functional layer is configured to increase the open circuit voltage of the solid oxide battery.

[0145] Appendix 47. The method according to any one of the sections or examples of this specification, particularly any one of appendices 26 to 46, comprising: the thickness of the porous functional layer along the first direction from the first electrode to the second electrode is about 20 μm or less; and / or A method, wherein the thickness of the non-porous oxide layer along the first direction is about 20 μm or less.

[0146] Note 48. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 47, comprising: The method, wherein the non-porous oxide layer comprises ceria, zirconia, bismuth oxide, or lanthanum gallate.

[0147] Appendix 49. The method according to any one of the sections or examples of this specification, particularly any one of appendices 25 to 48, comprising: The method, wherein providing (a), providing (b), providing (d), and / or providing (e) comprises tape casting, blade coating, lamination, screen printing, or any combination of the foregoing.

[0148] Note 50. The method according to any of the sections or examples herein, particularly any of Appendices 25 to 49, wherein (a) comprises: (a1) mixing about 60 wt. % nickel oxide (NiO) and about 40 wt. % gadolinium doped ceria (GDC) into a first slurry; (a2) mixing a pore-forming agent into the first slurry, the first slurry having a pore-forming agent corresponding to the porous support layer of the second electrode; (a3) mixing about 48 wt % NiO and about 52 wt % GDC into a second slurry, the second slurry corresponding to a porous functional layer of a second electrode;

[0149] Note 51. The method according to any of the sections or examples herein, particularly appendix 50, comprising: The method wherein the pore-forming agent comprises poly(methyl methacrylate).

[0150] Appendix 52. A solid oxide battery formed by the method described in any section or example herein, particularly any one of Appendices 25 to 51.

[0151] conclusion Any of the features shown or described herein, for example, with respect to Figures 1A-14D and Appendices 1-52, can be combined with any other features shown or described herein, for example, with respect to Figures 1A-14D and Appendices 1-52, to provide materials, systems, devices, structures, methods, and / or embodiments not otherwise shown or specifically described herein. All features described herein are independent of one another and can be used in combination with any other features described herein, except where structurally impossible. In view of the many possible embodiments to which the principles of the disclosed technology may be applied, it should be recognized that the illustrated embodiments are merely examples and should not be construed as limiting the scope of the disclosed technology. Rather, the scope is defined by the following claims. Accordingly, the inventors claim all that comes within the scope and spirit of these claims.

Claims

1. a non-porous oxide layer configured to conduct oxygen ions and act as a solid electrolyte; one or more first porous layers disposed on a first side of the non-porous oxide layer; one or more second porous layers disposed on a second side of the non-porous oxide layer opposite the first side; the non-porous oxide layer has a density greater than each of the first and second porous layers; the electronic conductivity of the non-porous oxide layer is less than 25% of the ionic conductivity of the non-porous oxide layer; for each of the first and second porous layers, the electronic conductivity of the respective porous layer is greater than 25% of the ionic conductivity of the respective porous layer; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to operate as a second electrode.

2. a non-porous oxide layer configured to conduct oxygen ions and act as a solid electrolyte; a porous functional layer disposed on the first surface of the non-porous oxide layer; one or more first porous layers disposed on a side of the porous functional layer opposite the non-porous oxide layer; one or more second porous layers disposed on a second side of the non-porous oxide layer opposite the first side; the non-porous oxide layer has a density greater than the density of the porous functional layer; the electronic conductivity of the non-porous oxide layer is less than 25% of the ionic conductivity of the non-porous oxide layer; the porous functional layer is effective to increase the ion mobility number of the non-porous oxide layer and the porous functional layer to at least 0.9 at a temperature of 550° C. or less; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to operate as a second electrode.

3. 3. The solid oxide battery of claim 1, wherein the one or more second porous layers comprise a nickel cermet of ceria, a nickel cermet of zirconia, or a mixed ionic electronic conducting oxide.

4. 4. The solid oxide battery of claim 3, wherein the one or more second porous layers are formed from a ceria nickel cermet, a zirconia nickel cermet, a gallate nickel cermet, a molybdate, a molybdate nickel cermet, a chromate, a chromate nickel cermet, a vanadate, or a vanadate nickel cermet.

5. The solid oxide battery of any one of claims 1 to 2, wherein the one or more first porous layers comprise ceria or bismuth oxide.

6. 6. The solid oxide of claim 5, wherein the one or more first porous layers comprise doped ceria, cubic bismuth oxide, rhombohedral bismuth oxide, or doped rhombohedral bismuth oxide.

7. 7. The solid oxide battery of claim 6, wherein the one or more first porous layers comprise doped ceria doped with one or more lanthanides.

8. 8. The solid oxide battery of claim 7, wherein the one or more lanthanides added are praseodymium, samarium, or both praseodymium and samarium.

9. 6. The solid oxide cell of claim 5, wherein the one or more first porous layers are infiltrated with one or more electrocatalyst oxides.

10. 10. The solid oxide cell of claim 9, wherein the one or more electrocatalyst oxides comprise one or more multi-phase electrocatalysts formed by at least A and B, and a molar ratio of A to B in the one or more multi-phase electrocatalysts is about 1:

1.

11. 11. The solid oxide battery of claim 10, wherein A is a Group 2 element, Group 3 element, or a lanthanide and B is a Period 4 element.

12. A is selected from the group consisting of praseodymium (Pr), calcium (Ca), strontium (Sr), yttrium (Y), lanthanum (La), neodymium (Nd), samarium (Sm), dysprosium (Dy), and erbium (Er); 12. The solid oxide battery of claim 11, wherein B is selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and zinc (Zn).

13. 10. The solid oxide battery of claim 1, wherein the one or more first porous layers comprise ceria, bismuth oxide, or a composite material formed from (i) ceria or bismuth oxide and (ii) one or more electronically conductive and electrocatalytic oxides.

14. The one or more first porous layers may be made of lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt ferrite (LSCF), yttria stabilized zirconia (YSZ), scandia stabilized zirconia (SSZ), gadolinia doped ceria (GDC), samaria doped ceria (SDC), samaria neodymium doped ceria (SNDC), erbia stabilized bismuth oxide (ESB), dysprosium tungsten stabilized bismuth oxide (DWSB), yttria stabilized bismuth oxide (YSB), rhombohedral bismuth oxide, strontium and magnesium doped lanthanum gallate (LSGM), strontium samarium cobalt oxide, and Ln nickelate. 2 NiO 4+δ 10. The solid oxide battery of claim 1 comprising a material selected from the group consisting of: (Ln is a lanthanide).

15. 10. The solid oxide battery of claim 1 further comprising a porous functional layer disposed between and in direct contact with one of the first porous layers and the non-porous oxide layer.

16. 16. The solid oxide battery of claim 2, wherein the porous functional layer consists essentially of ceria or bismuth oxide.

17. 16. The solid oxide battery of claim 2, wherein the porous functional layer is configured to increase an open circuit voltage of the solid oxide battery.

18. 18. The solid oxide battery of claim 17, wherein the open circuit voltage is 0.9 V or more at 500-550° C.

19. the thickness of the porous functional layer along the first direction from the first electrode to the second electrode is less than or equal to about 20 μm; and / or 16. The solid oxide battery of claim 2, wherein the thickness of the non-porous oxide layer along the first direction is about 20 μm or less.

20. At least one of the one or more second porous layers is configured to operate as an anode and at least one of the one or more first porous layers is configured to operate as a cathode when electrochemical oxidation occurs on the second side; and / or 3. The solid oxide battery of claim 1, wherein at least one of the one or more second porous layers is configured to operate as a cathode and at least one of the one or more first porous layers is configured to operate as an anode when reduction occurs on the second side.

21. the one or more first porous layers are configured to receive an input stream having an oxygen concentration in the range of 20 to 100% (mole fraction), inclusive; 3. The solid oxide cell of claim 1, wherein the one or more second porous layers are configured to receive a fuel, and the solid oxide cell is configured to operate as a solid oxide fuel cell (SOFC) by electrochemically oxidizing the fuel to produce electricity.

22. The one or more second porous layers are 2 O and / or CO 2 configured to receive an input stream comprising: The solid oxide cell is charged with H on the second side. 2 O or CO 2 is electrochemically reduced to O on the first side 2 3. The solid oxide cell of claim 1 , configured to operate as a solid oxide electrolysis cell (SOEC) by generating

23. the solid oxide cell is configured to reverse polarization to switch between operation as a solid oxide fuel cell (SOFC) and operation as a solid oxide electrolysis cell (SOEC); The solid oxide battery comprises a first operating mode, a second operating mode, and a third operating mode. The solid oxide battery comprises a first operating mode and a second operating mode. 2 O and / or CO 2 to produce a fuel, and wherein during a second mode of operation the solid oxide cell is configured to oxidize the fuel to produce electricity.

24. The solid oxide battery of any one of claims 1 to 2, wherein the non-porous oxide layer comprises ceria, zirconia, bismuth oxide, or lanthanum gallate.

25. 1. A method of manufacturing a solid oxide battery, comprising: (a) providing one or more first precursors for forming one or more second porous layers; (b) providing one or more second precursors for forming a non-porous oxide layer on the one or more first precursors; (c) sintering the first and second precursors at a temperature equal to or greater than the first threshold to form one or more second porous layers on a second side of the non-porous oxide layer; (d) providing one or more third precursors for forming one or more first porous layers on a first side of the non-porous oxide layer opposite the second side; (e) sintering the one or more third precursors at a temperature below a first threshold to form one or more first porous layers on the first side of the non-porous oxide layer; the non-porous oxide layer has a density greater than the densities of the first and second porous layers; The non-porous oxide layer has, for each of the first porous layer and the second porous layer, an electronic conductivity of each porous layer that is greater than 25% of an ionic conductivity of each porous layer; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to act as a second electrode.

26. 1. A method of manufacturing a solid oxide battery, comprising: (a) providing one or more first precursors for forming one or more second porous layers; (b) providing one or more second precursors for forming a non-porous oxide layer on the one or more first precursors; (c) sintering the first and second precursors at a temperature equal to or greater than the first threshold to form one or more second porous layers on a second side of the non-porous oxide layer; (d) providing one or more third precursors for forming a porous functional layer on a first side of the non-porous oxide layer opposite the second side; (e) providing one or more fourth precursors for forming one or more first porous layers on the one or more third precursors; (f) sintering the third and fourth precursors at a temperature below a first threshold to form a non-porous oxide layer on a first side of the non-porous oxide layer and to form the first porous layer on a side of the non-porous oxide layer opposite the first porous layer; the non-porous oxide layer has a density greater than the densities of the first and second porous layers; the non-porous oxide layer has, for each of the first and second porous layers, an electronic conductivity of each porous layer that is greater than 25% of an ionic conductivity of each porous layer; The porous layer has an effect of increasing the ion migration number of the non-porous oxide layer and the porous functional layer to at least 0.9 at a temperature of 550° C. or less; At least one of the one or more first porous layers is configured to operate as a first electrode; At least one of the one or more second porous layers is configured to act as a second electrode.

27. The method of any one of claims 25 to 26, wherein the first threshold is about 1000°C.

28. sintering of the one or more third precursors or the third and fourth precursors is carried out at a temperature of about 950° C.; Sintering of the first and second precursors is carried out at a temperature of about 1450° C.; or 28. The method of claim 27, wherein both of the above are performed.

29. The method of any one of claims 25-26, wherein the one or more second porous layers comprise a nickel cermet of ceria, a nickel cermet of zirconia, or a mixed ionic electronic conducting oxide.

30. 30. The method of claim 29, wherein the one or more second porous layers are formed from a ceria nickel cermet, a zirconia nickel cermet, a gallate nickel cermet, a molybdate, a molybdate nickel cermet, a chromate, a chromate nickel cermet, a vanadate, or a vanadate nickel cermet.

31. The method of any one of claims 25 to 26, wherein the one or more first porous layers comprise ceria or bismuth oxide.

32. 32. The method of claim 31 , wherein the one or more first porous layers comprise doped ceria, cubic bismuth oxide, rhombohedral bismuth oxide, or doped rhombohedral bismuth oxide.

33. 33. The method of claim 32, wherein the one or more first porous layers comprise one or more lanthanide-doped doped ceria.

34. 34. The method of claim 33, wherein the one or more lanthanides added are praseodymium, samarium, or both praseodymium and samarium.

35. 32. The method of claim 31 , further comprising, after forming the one or more first porous layers, infiltrating at least one of the one or more first porous layers with one or more electrocatalytic oxides.

36. 36. The method of claim 35, wherein the infiltration comprises: (f1) providing a dose of one or more electrocatalysts in solution to at least one of the one or more first porous layers; (f2) exposing at least one of the one or more first porous layers having the dose to a vacuum; (f3) repeating (f1) and (f2) with another dosage of one or more electrocatalysts in the solution; and (f4) after (f3), exposing the one or more first porous layers to a temperature of about 450° C. to vaporize or combust the solution.

37. 36. The method of claim 35, wherein the one or more electrocatalyst oxides comprise one or more multi-phase electrocatalysts formed by at least A and B, and wherein a molar ratio of A:B in the one or more multi-phase electrocatalysts is about 1:

1.

38. 38. The method of claim 37, wherein A is a Group 2 element, Group 3 element, or a lanthanide and B is a Period 4 element.

39. A is selected from the group consisting of praseodymium (Pr), calcium (Ca), strontium (Sr), yttrium (Y), lanthanum (La), neodymium (Nd), samarium (Sm), dysprosium (Dy), and erbium (Er); and / or 39. The method of claim 38, wherein B is selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and zinc (Zn).

40. (d) providing one or more third precursors, (d1) mixing ceria with or without one or more lanthanide oxides into the ink; (d2) mixing a pore-forming agent into the ink; 32. The method of claim 31 , comprising:

41. 41. The method of claim 40, wherein the pore former comprises poly(methyl methacrylate).

42. 27. The method of any one of claims 25-26, wherein the one or more first porous layers comprise ceria, bismuth oxide, or a composite material formed from (i) ceria or bismuth oxide with one or more electronically conductive and electrocatalytic oxides.

43. The one or more first porous layers may be made of lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt ferrite (LSCF), yttria stabilized zirconia (YSZ), scandia stabilized zirconia (SSZ), gadolinia doped ceria (GDC), samaria doped ceria (SDC), samaria neodymium doped ceria (SNDC), erbia stabilized bismuth oxide (ESB), dysprosium stabilized bismuth oxide (DWSB), yttria stabilized bismuth oxide (YSB), rhombohedral bismuth oxide, strontium and magnesium doped lanthanum gallate (LSGM), strontium samarium cobalt oxide (SSC), and Ln nickelate. 2 NiO 4+δ The method of any one of claims 25 to 26, comprising a material selected from the group consisting of: (Ln is a lanthanide).

44. prior to (d), providing one or more fourth precursors for forming a porous functional layer on the first surface of the non-porous oxide layer; Providing (d) includes providing one or more third precursors on the one or more fourth precursors; 26. The method of claim 25, wherein the sintering in (e) forms the one or more fourth precursors as a porous functional layer disposed between and in direct contact with one of the first porous layer and the non-porous oxide layer.

45. 45. The method of any one of claims 26 and 44, wherein the porous functional layer consists essentially of ceria or bismuth oxide.

46. 45. The method of any one of claims 26 and 44, wherein the porous functional layer is configured to increase the open circuit voltage of the solid oxide battery.

47. the thickness of the porous functional layer along the first direction from the first electrode to the second electrode is less than or equal to about 20 μm; and / or 45. The method of any one of claims 26 and 44, wherein the thickness of the non-porous oxide layer along the first direction is about 20 μm or less.

48. The method of any one of claims 25 to 26, wherein the non-porous oxide layer comprises ceria, zirconia, bismuth oxide, or lanthanum gallate.

49. 27. The method of any one of claims 25-26, wherein providing (a), providing (b), providing (d), and / or providing (e) comprises tape casting, blade coating, lamination, screen printing, or any combination of the foregoing.

50. 27. The method of any one of claims 25 to 26, wherein (a) comprises: (a1) mixing about 60 wt. % nickel oxide (NiO) and about 40 wt. % gadolinium doped ceria (GDC) into a first slurry; (a2) mixing a pore-forming agent into the first slurry, the first slurry having a pore-forming agent corresponding to the porous support layer of the second electrode; (a3) mixing about 48 wt % NiO and about 52 wt % GDC into a second slurry, where the second slurry corresponds to a porous functional layer of a second electrode;

51. 51. The method of claim 50, wherein the pore former comprises poly(methyl methacrylate).